A novel approach for assessing the genuine thermal efficiency of high-pressure grinding roller (HPGR) crusher based on exergy analysis - Zhengyu Liu; Zhihao Liu; Xiaoming Liu; Bin Yang; Wei Liu; Jiawei Lin; Siqi Zhang; Wenjie Zou; Jun Zhang; Jinrong Ju; Jue Kou; Chunbao Sun; et al. (Minerals Engineering, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Revisiting nitrite sensitized photolysis for micropollutants removal: overlooked oxidative mechanisms of reactive nitrogen species and their dual role in byproduct toxicity - Zhilin Zhang; Sicheng Gong; Yiqi Liu; Qingyang Jiang; Zhongyue Sun; Wei Zhuang; Junhao Lin; Jiawei Liu; Zhichao Liu; Tonghao Yuan; Jun Shi; Huiping Deng (Water Research, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

Mesozoic crustal thinning in the northern North China Craton: Evidence from Triassic and Jurassic plutons in the Huyu area, northwestern Beijing - Liang Qiu; Dan-Ping Yan; Jun-Ting Qiu; Wei Yang; Yiyu Lin; Suhua Cheng; Xiuhua Cao; Xuchao Chai; Pei Zhang; Lei Gao; Zeyilin Ma (Journal of Asian Earth Sciences, 2026)

Engineering Chlorella-based consortia for sustainable food wastewater treatment: nutrient recovery, pollutant degradation and advanced harvesting - Lin Zhao; Shujie Wei; Yifan Zhang; Luguang Tao; Yuwei Xu; Yiming Wang; Zhangli Hu; Jun Tang; Song Wang (Environmental Research, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Crystallinity-dependent PMS activation by ZnFe2O4 spinel enables radical-dominated degradation of imidacloprid under microwave irradiation - Yang Zhou; Xitao Liu; Jun Huang; Yanwei Zhao; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Chemical Engineering Journal, 2026)

W-PDA/Au nanohybrid-based ternary immunosensor for simultaneous detection of PCT, IL-6, and CRP toward efficient sepsis diagnosis - Lin Jin; Yi Shen; Wei Jin; Xu Tao; Jinwu Hu; Shujuan Mao; Jin tao Li; Hui-jun Li; Ding Wang; Yuan Zhang; Bin He (Chemical Engineering Journal, 2026)

Cas13a-assisted semi-contact technology combined PtPd nanozyme for ultrasensitive and visual tsRNA detection - Gaihua Cao; Wei Xu; Jun Ren; Qin Liu; Pan Zhao; Faliang Cao; Lin Xia; Xi Zhang (Chemical Engineering Journal, 2026)

Engineered bacteria as ultrasound-responsive carbon monoxide vehicles for Cancer gas therapy and synergistic immunotherapy - Xiaorui Chen; Xiao Xiao; Wei Zhao; Bin Liu; Hongzhou Lian; He Ding; Piaoping Yang; Ping'an Ma; Lingjie Song; Shifang Luan; Ziyong Cheng; Jun Lin (Chemical Engineering Journal, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Albafurans D−N, 2-phenylbenzofuran derivatives with anti-inflammatory activity from Morus alba - Jun-Sheng Zhang; Lin-Lin Tian; Quan-Hao Wei; Meng-Jie He; Hua Zhang (Phytochemistry, 2026)

Precise radical quantification and process optimization of UV/persulfate advanced oxidation for sertraline removal - Xiaofeng Zeng; Wenbo Ren; Xitao Liu; Yanwei Zhao; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Journal of Environmental Chemical Engineering, 2026)

Multifunctional MnO2-based nanozyme scaffold with microenvironment-responsive release for immunomodulation and neuroregeneration in spinal cord injury applications - Ling Peng; Yusong Pan; Jun Tao; Cuilian Wei; Qianqian Liu; Run Huang; Xiuling Lin; Rui Yue (Chemical Engineering Journal, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Directional disparity between oysters and mud snails in modulating marine carbon sequestration - Zhou Zhang; Xuan Dong; Yu-Jia Lei; Zhi-Yong Guo; Shuang-Jie Tian; Chang-Lin Li; Miao-Jun Pan; Xiang-Li Tian; Yun-Wei Dong; Jing-Yu Li; Shuang-Lin Dong (Journal of Environmental Management, 2026)

Reannotation of the ABCC transporters reveals a miR-980-BdABCC1 regulatory axis driving avermectin tolerance in Bactrocera dorsalis - Hou-Ji Song; Lin Wang; Wei Zhao; Guy Smagghe; Jin-Jun Wang; Dan-Dan Wei (Insect Biochemistry and Molecular Biology, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Dual enhancement of carbon-based catalysts via Maillard reaction: Boosting peroxymonosulfate activation and facilitating 1O2 production - Xiaoyu Ma; Xitao Liu; Jun Huang; Yanwei Zhao; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Chemical Engineering Journal, 2026)

Multi-stimuli responsive cellulose nanocrystal-based microcapsules with enhanced insecticidal efficacy and environmental safety - Er-min Zhou; Jia-wei Ding; Dao-bing Kang; Yi-lin Tan; Yong-jiang Li; De-qiang Li; Jun Li (Carbohydrate Polymers, 2026)

PFOA promotes PMAIP1–MCL1 apoptotic vulnerability within a BHLHE41-associated macrophage regulatory architecture in atherosclerosis - Hou-liang Chen; Run Wang; Wei-jun Tao; Wang Zhang; Yan-lin Gao; Xiao-bing Cheng (Chemico-Biological Interactions, 2026)

Microplastic type influences soil phosphorus availability independently of long-term cropping systems and fertilization regimes - Xuechen Yang; Lin Han; Raúl Ochoa-Hueso; Jingjie Dou; Peng He; Yakov Kuzyakov; Wenzheng Song; Xiaowei Wei; Yueyu Sui; Xiangxiang Hao; Lu-Jun Li (Agriculture, Ecosystems & Environment, 2026)

Species-specific greenhouse gas emissions and carbon budgets in freshwater monoculture ponds - Zhao-Jun Yong; Wei-Jen Lin; Yao-Chen Lee; Yen-Cheng Liang; Shuenn-Der Yang; Hsing-Juh Lin (Aquaculture International, 2026)

Wheat germ protein in functional foods: structure, processing, applications, and mechanistic insights - Long Pan; Jing-Yang Cai; Ai-Mei Liao; Lin-Lin Ding; Yin-Chen Hou; Ji-Hong Huang; Xin Wang; Ya-Wei Zhao; Na Liu; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Toward clinically integrated computational pathology: advancing diagnostic insight and practice transformation - Bonan Chen; Xin Fang; Weiru Yu; Jialin Wu; Canbin Fang; Yuanke Liang; Jun Yu; Gary M.K. Tse; Ka Fai To; Haoyu Lin; Wei Kang (Science Bulletin, 2026)

Carbon footprint accounting in green leather processing: methodological challenges, environmental trade-offs, and circular pathways - Minmin Liu; Chunhua Wang; Fengteng Zhang; Jun Sang; Yuanhang Xiao; Wei Lin (Resources, Conservation and Recycling, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

The impact of low ambient pressure on the cavitation erosion intensity of aluminum alloy materials - Jian-Bo Li; Yong Xia; Wei-Lin Xu; Jun Deng; Jun Chen; Zhen-Yu Du (Ocean Engineering, 2026)

Transformation characteristics of typical antidepressants in UV-advanced oxidation processes - Wenbo Ren; Xitao Liu; Yanwei Zhao; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang; Shouliang Huo (Journal of Hazardous Materials, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Design, preparation and performance study of DAP-1 based conductive energetic composite - Wan-Jun Wei; Rui Pu; Yu-Ruizhi Lin; Ying-Qi Mao; Qi-Long Yan; Shao-Li Chen (Chemical Engineering Journal, 2026)

In situ mapping of rhizosphere processes: biochar-mediated cadmium immobilization and rhizosphere microenvironment regulation - Baoying Wang; Zhao Wei; Haitao Sun; Xing Liu; Li Zhang; Jianyu Lin; Jun Luo (Journal of Soils and Sediments, 2026)

Effects of varying temperature and salinity levels on the emission of short-lived halocarbons and dimethyl sulfide from selected tropical green seaweeds - Tinesa Krishnan; Fiona Seh-Lin Keng; Siew-Moi Phang; Choon-Weng Lee; Yee-Jun Tham; Hui-Yin Yeong; Chui-Wei Bong; Gill Malin (Algal Research, 2026)

Effects of Non-Uniform Hanging-Depth Layouts on Hydrodynamics and Mass Transport in Suspended Mussel Farms - Yiquan Zhen; Wei Zhong; Yanjiao Li; Kaitao Zhou; Jing Zhao; Jun Lin (Journal of Marine Science and Engineering, 2026)
In suspended mussel farms, culture-layer food supply can be limited, whereas the 4–8 m subsurface layer is rich in particulate organic matter and seston. Using a representative aquaculture block off Gouqi Island, China, this study examined the hydrodynamic and transport effects of non-uniform hanging-depth layouts. The 0° uniform-depth layout was the reference. Five configurations were modeled: V-shaped, inverted V-shaped, uniform-depth (90° inflow), V-shaped (extended), and inverted V-shaped (extended). Flume PIV validated the model. Simulations used uniform and measured velocity-profile inflows, with and without density stratification; a passive tracer tracked seston-rich water from the 4–8 m layer. Uniform-depth hanging formed a low-velocity zone in the sleeve layer, limiting water exchange. Non-uniform layouts altered drag distribution and promoted tracer redistribution into overlying 3–5 m waters. In the V-shaped configuration, water was guided upward along sleeve bottoms in the downstream half of the aquaculture block (S2), where pronounced redistribution within the aquaculture block resulted in a tracer concentration of approximately 0.1362 in the 2–3 m layer. Stratification constrained upward spreading, whereas extended configurations may limit food replenishment through enhanced upper-layer blockage and filtering effects. Low-Richardson-number regions corresponded with tracer uplift and enhanced spreading, indicating local shear. Overall, the V-shaped configuration balanced in-farm replenishment, downstream transport, and flow maintenance without additional sleeve length.

Subduction-controlled Late Triassic rifting along the northern margin of Gondwana - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Yang Wang; Jun-Pu Lv; Xin-Yu Hou (International Geology Review, 2026)

Non-Equilibrium Recovery of Plankton Communities in the Yangtze River Estuary: Three Years After the Fishing Ban - Bangping Deng; Wei Liu; Qiliang Song; Yuchen Guo; Chenxing Yang; Lin Zhu; Jun Li; Lijia Liu; Yin Yang; Xiucheng Yu (Fishes, 2026)
Large-scale fishing bans are increasingly implemented to restore aquatic ecosystems, yet their effects on lower trophic levels remain poorly understood. As one of the world’s largest estuarine systems, the Yangtze River Estuary has been subjected to a ten-year fishing ban since 2021, providing a unique opportunity to potentially examine the response of plankton community to reduced fishing pressure along a steep salinity–nutrient gradient. This study relies on one-off environmental and plankton field surveys conducted in autumn 2024 (a sampling instead of multi-year time-series monitoring), we applied redundancy analysis, Mantel tests, and threshold indicator taxa analysis to tentatively clarify the roles of nutrients and salinity in structuring post-ban plankton communities. Species richness may have increased substantially compared with pre-ban levels, but community evenness declined and the dominance of Skeletonema costatum could have intensified, revealing a possible non-equilibrium recovery pattern. Zooplankton density increased substantially, which may not be fully consistent with the expectation under a simple top-down release scenario. Threshold analysis showed that S. costatum exhibited bidirectional responses to dissolved inorganic nitrogen and phosphate, with its positive response thresholds matching ambient nutrient concentrations in the inner estuary; this discrepancy is only a plausible inference since we lack direct measurements of fish predation and zooplankton grazing rates to verify causal trophic interactions. Our findings suggest that bottom-up forces driven by persistent eutrophication remain the dominant control on plankton community structure three years after the ban. From a watershed management perspective, our observational results provide a tentative implication that substantial reductions in nutrient loading might be required to mitigate unbalanced plankton community recovery; otherwise, the structural integrity of plankton assemblages could lag far behind the recovery of species richness under the current eutrophic background.

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Effects of dietary Zn deficiency and excess on growth performance, glycolipid metabolism, and intestinal homeostasis of juvenile golden pompano (Trachinotus ovatus) - Hongkai Ye; Zhanzhan Wang; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Aquaculture International, 2026)

A Large-Scale Micro-friction True Triaxial Apparatus for Analyzing the Failure Features of Coarse-Grained Soils Under Complex Stress Conditions - Jia-Jun Pan; Wei Zhao; Zhan-Lin Cheng; Yong-Zhen Zuo (Rock Mechanics and Rock Engineering, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Environmental controls and nonlinear responses of the diatom-dinoflagellate ratio in Jiaozhou Bay - Yipeng Huang; Zhengguo Cui; Changhua Liu; Dongsheng Ding; Lin Zhu; Keming Qu; Yuqiu Wei; Jun Sun (Marine Pollution Bulletin, 2026)

Deciphering the spatial patterns of a springtime microbial community: Structure, function, and key drivers in the Southern Yellow Sea - Yang Yuan; Wei He; Long Jiang; Lin-Qiong Wang; Xian-Pu Ji; Dao-Feng Zhang; Wen-Jun Li (Journal of Environmental Sciences, 2026)

Lanthanum-modified biochar for dual removal of particulate/dissolved phosphorus in agricultural runoff: Performance and reuse as slow-release fertilizer - Ting Chen; Jiayi Lu; Fenghao Lin; Zhiqiang Chen; Junjie Wei; Jie He; Ying Wang; Xiujuan Tang; Jun Yin (Journal of Environmental Sciences, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Engineering a siderophore-macrolide conjugate via Trojan horse strategy for targeting Pseudomonas aeruginosa and related resistant pathogens - Chun-Yan Zhang; Wei-Min Chen; Guo-Bin Yang; Jing-Hua Wei; Zu-Ju Liang; Xi-Bing Hu; Ping Lan; Jing Lin; Jun Liu (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Intermittent Theta-Burst Stimulation (iTBS) Improves Motor Coordination and Modulates Neuroinflammation and Autophagy in SCA3/MJD Mice - Le-Wen Chen; Yan-Hua Lian; Xiao-Lei Dong; Kai-Liang Luo; Li-Qiong Zhan; Li-Li Xie; Qi-Kui Sun; Wei Lin; Shi-Rui Gan; Xiao-Ping Cheng; Jun Ni; Xin-Yuan Chen (The Cerebellum, 2026)

Integrating deep learning and groundwater dynamics for drought vulnerability assessment under climate scenarios - Wei Sun; Li-Chiu Chang; Jun Jie Lin; Fi-John Chang (Groundwater for Sustainable Development, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Mechanistic insights into the effects of roasting on heat-induced hazard formation and lipid oxidation stability in camellia seeds - Tongqiang Chen; Xiaojuan Wu; Jun Xiang; Helin Li; Kailong Li; Haizhi Wu; Wenjie Tang; Can Li; Qinlu Lin; Wei Wu (Food Chemistry, 2026)

Identification of the chili powder with illegal additive Sudan I by shifted-excitation Raman difference spectroscopy system - Shu-Wei Hu; Jun-Qin Xu; Yan-Chi Chao; Jhen-Yue Chang; Ding-Zheng Lin (Food Chemistry, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Sn2+ doping-induced activation of inert adsorption sites in Li/Al-LDHs for selective lithium extraction from brines - Rui Zhang; Chenlu Yan; Jun Chen; Ting Wei; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Co-solvent-modulated polyamide nanofiltration membranes for high-temperature separation - Wan-Long Li; Xiao-Wei Luo; Wan-Ting Lin; Si-Yuan Zhang; Zi-Lu Zhang; Zi-Jun Zhang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2026)

Enhancing Fenton-like degradation with Co1-xS@C under neutral and alkaline environment: Unveiling the role of reactive microenvironment - Xiaoyu Ma; Xitao Liu; Jun Huang; Yanwei Zhao; Chunye Lin; Mengchang He; Wei Ouyang (Chemical Engineering Journal, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Interaction between stocking density and hydrodynamic on the growth of Mytilus coruscus in suspended cultures - Yue Wu; Guanlin Yang; Wei Zhong; Xiang Zhang; Jing Zhao; Jun Lin (Aquaculture, 2026)

Rapid elimination of harmful cyanobacteria via synergistic effects of photo-oxidation and flocculation - Yuanyuan Xu; Shiqi Tian; Ruihua Cao; Wei Lin; Jun Ma; Gang Wen (Water Research, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

A novel mechanism of uranium mineralization: The role of zircon adsorption at the Qigequan deposit, Qaidam Basin, NW China - Yi-Han Lin; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Zhe Chi; Zhi-Lin Cheng; Wen-Yi Wu; Chen Zhang; Bing-De Qi; Xue-Bin Wei (Sedimentary Geology, 2026)

Comparing the performance of different hyperspectral satellite imaging spectroscopy in mapping methane point-source emissions - Fei Li; Keer Lin; Yingqi Yan; Shengxi Bai; Qidan Huang; Chenxi Feng; Shiwei Sun; Shaohua Zhao; Wei Zhou; Chunyan Zhou; Jun Lin; Xinwei Zhang; et al. (Remote Sensing of Environment, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Early evolution of the Meso-Tethys Ocean: Constraints from Permo-Triassic flysch deposits - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Xin-Yu Hou; Yang Wang; Li-Qiang Zhang (Gondwana Research, 2026)

Space weathering on the lunar nearside and farside revealed by iron and potassium isotopes - Heng-Ci Tian; Wei Yang; Xinmiao Zhao; Jun Du; Liyu Shan; Wen-Jun Li; Jing Wang; Xuhang Zhang; Yangting Lin; Xian-Hua Li; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Uncovering biases in standard occupancy assumptions using urban-scale mobile signaling data - Shuyi Chen; Yihu Zhang; Jun Xiao; Ziliang Wei; Yangyang Wang; Yixing Chen; Hao Zhou; Yang Geng; Borong Lin (Building and Environment, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Research on rule of law system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area - Ke Zhang; Er-He Chen; Yu-Lin Chen; Jun-Jie Li; Tao Huang; Wei Liu; Si-Hao Wei; Yu-Kang Tu (Frontiers in Marine Science, 2026)
The development of a legal system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area is a critical issue for cross-border ecological governance under the unique context of "One Country, Two Systems, Three Jurisdictions." This issue directly affects regional ecological security and the high-quality development of the marine economy. This paper uses comparative law and empirical analysis to systematically review the institutional frameworks and current practices of the three regions across four dimensions: Legislation, law enforcement, judicial adjudication, and legal regulation of public participation. The study finds that the current system faces core difficulties, including a disconnect in legislative coordination mechanisms, insufficient effectiveness in joint law enforcement, uncoordinated judicial collaboration, and insufficient legal safeguards for public participation. The root causes lie in the differences between regional legal systems, the absence of coordination mechanisms, poor resource integration, and fragmented participation channels. Based on this, the paper proposes a comprehensive improvement path. At the legislative level, we should establish a normalized coordination mechanism to promote the alignment of rules and standards. At the enforcement level, we should build a unified coordination platform to deepen cross-border collaboration and resource sharing. At the judicial level, we should improve cross-border collaboration norms and improve mechanisms for identifying and repairing ecological damage. At the level of public participation, we should build a unified cross-border platform to strengthen collaborative systems and public interest cooperation. The research aims to provide a governance model for regional marine environmental protection under "One Country, Two Systems, Three Jurisdictions," offering theoretical support and practical guidance for solving cross-border ecological governance problems, and assisting in the construction of a strong maritime nation and the improvement of the global marine governance system.

Microplastics enhance soil nitrogen availability by stimulating nitrogen-acquiring enzyme activity over three decades-long fertilization regimes - Lin Han; Jingjie Dou; Kai Zhu; Lu-Jun Li; Peng He; Xiaowei Wei; Xiaojing Hu; Yueyu Sui; Xiangxiang Hao; Xuechen Yang (Soil and Tillage Research, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Optimizing collaborative management decision-making in large watersheds through seasonal dynamic water quality diagnosis - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Ji-Wei Pang; Nan-Qi Ren; Shan-Shan Yang (Journal of Cleaner Production, 2026)

Systematic assessment and improvement for the intelligent municipal solid waste sorter - Wei-Lung Mao; Shu-Han Huang; Hsu-Cheng Chen; Jun-Wei Zeng; Yu-Hao Lin (Journal of Cleaner Production, 2026)

Life cycle environmental impacts of alkaline regulator substitution in electroplating wastewater treatment - Zhiyu Zhang; Fangkun Lin; Tianqi Ji; Nizar Talty; Jun Chen; Wei Zhang; Ghada Eshaq; Xin Yu; Ka Leung Lam; Huabin Zeng (Environmental Research, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Multiscale modeling and swelling behaviors of Wyoming sodium montmorillonite systems - Zhi-jun Zhang; Jin-xiang Deng; Chang-fu Wei; Ya-kun Tian; Lin Hu; Min Wang; Ling-ling Wu; Kai-wen Tong (Computers and Geotechnics, 2026)

Tunable synthesis of tailored high-energy-density fuels from coal-based fluorene - Bing-Wei Chen; Hua-Jun Zhai; Yan-Cheng Hu; Yan-Hong Tan; Jia Li; Zhilian Wu; Lin Shao; Jing-Pei Cao (Chemical Engineering Journal, 2026)

Electric field superposition for efficient implantable ultrasound energy harvesting - Aokai Yang; Chaoran Tan; Yuyang Lin; Haoying Han; Renfei Wei; Yan Wang; Kang Chen; Shizhe Lin; Liang Huang; Jun Zhou (Chemical Engineering Journal, 2026)

Nitrogen removal driven by zonal supply of thiosulfate and pyrite in an up-flow blanket filter (UBF) reactor - Qian Zhang; Lan Lin; Tingsheng Hu; Qianyi Liu; Ying Wang; Haozhe Mo; Wenbiao Jin; Wei Zhang; Jun Chen; Huabin Zeng; Xiaojun Wang; Shaohua Chen; et al. (Bioresource Technology, 2026)

Dual phosphorylation of DISC1 at Ser58 and Ser713 regulates polarization of cortical neurons via GSK3β - Jun Ren; Yiliang Xu; Lin Yuan; Yingxin Liu; Qian Chu; Tian Zhao; Wei Zhang; Jing Tian; Shi-Qiang Wang; Haihong Ye (Science China Life Sciences, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Microinterface effects of catalytic materials on PMS/PDS-mediated degradation of organic pollutants: Mechanistic insights, structural influences, and enhancement strategies - Yifan Chen; Jingyi Sun; Bingjie Yan; Yihe Wang; Zhengda Lin; Wei Zuo; Yu Tian; Jun Zhang (Water Research, 2026)

Climate change-induced floods disrupt intercity mobility in China: A national-scale assessment - Qian Yao; Can Lu; Mengya Li; Wei Zhai; Jiangyang Lin; Hanqing Xu; Qing Liu; Jun Wang (Travel Behaviour and Society, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Modeling water quality in tidal reaches under data-scarce conditions: enhancing aquaculture carrying capacity in bays through upstream contamination control - Fangkun Lin; Zhipeng Luo; Zhiyu Zhang; Jun Chen; Wei Zhang; Lijun Liang; Ghada Eshaq; Xin Yu; Huabin Zeng (Journal of Hydrology, 2026)

Nonlinear microbial nutrient limitation responses to biodegradable vs. conventional microplastics under long-term agricultural management - Jingjie Dou; Lin Han; Xiaojing Hu; Lu-Jun Li; Peng He; Junhui Wang; Xiangxiang Hao; Yueyu Sui; Wei Sun; Xuechen Yang (Journal of Hazardous Materials, 2026)

Dietary chromium picolinate alleviates hypoxia-induced liver inflammation in juvenile grass carp (Ctenopharyngodon idella): Involving the synergistic regulation of ion homeostasis and mitochondrial DNA integrity - Chuan-Shuai Xiong; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Hong-Yun Zhang; Jun Jiang; Xiao-Qiu Zhou; Pei Wu (Fish & Shellfish Immunology, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Recent advances in fabrication and application of lignocellulose-based polyurethane - Jingjing Wu; Chunhua Wang; Keshuai Ren; Jun Sang; Yuanhang Xiao; Huining Xiao; Wei Lin (Carbohydrate Polymers, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

An Integrated Machine Learning and Remote Sensing Method for Predicting Cyanobacterial Blooms: A Case Study in China’s lakes along a large-scale water diversion project - Yue Zhang; Jun Hou; Lin Lan; Zheng Wu; Hanzhi XU; Jun Wu; Guoxiang You; Wei Ding; Qianqian Zheng; Lingzhan Miao (Environmental Management, 2026)

Excavation-induced soil disturbance assessment of soft clay behind the diaphragm wall - Yan-Guo Zhou; Mu-Zhi Li; Yu Tian; Jun-Neng Ye; Wei-An Lin; Yun-Min Chen (Tunnelling and Underground Space Technology, 2025)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

A unified framework for predicting vertical bearing capacity of fully embedded pipes/tunnels in clay seabed based on the undrained failure mechanisms - Yu Zhao; Xing-Tao Lin; Wei-Jian Li; Jun-Chen Zhang; Zhi-Yao Tian; Quan-Mei Gong (Ocean Engineering, 2025)

Numerical simulation on the migration patterns of stock-enhanced jellyfish (Rhopilema esculentum) in the offshore wind farms and cross-sea bridges area of Hangzhou Bay - Haihui Yang; Wei Zhong; Yanjiao Li; Jiaxuan Mao; Zhenhua Wang; Jun Lin (Ocean Modelling, 2025)

Perinatal maternal lead exposure induces intergenerational neurotoxicity via mitochondrial dysfunction and mediation by perturbation of thyroid function - Lin Zhang; An-Xin Lu; Ling Li; Qian Wei; Yin Lin; Jun-Xia Liu; Li Ma; Ren-Tong Chen; Bin Luo; Chong-Huai Yan (Journal of Hazardous Materials, 2025)

Cradle-to-gate carbon footprint of industrial-scale fermentative production of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH) - Hsien-Tse Chen; Yu-Hsiang He; Pei-Yi Lin; Wei-Shu Huang; Kaarmukhilnilavan R. Srinivasan; Jun-You You; Pei-Yu Sun; Allen H. Hu; Penjit Srinophakun; Maythee Saisriyoot; Si-Yu Li (Journal of Cleaner Production, 2025)

Preparation of sodium alginate/sodium carboxymethyl cellulose composite coating film and evaluation of its effects on mango preservation - Wei Wang; Jiakai Yu; Yuting Huang; Bai-Jun Li; Wenzhu Shen; Wenli Zhang; Yining Xia; Qiong Lin (Food Chemistry, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Functional characterization of the heat shock protein gene hsp78 in regulating carotenoid biosynthesis in the edible-medicinal fungus Cordyceps militaris - Zi-Qing Liang; Yi Zhao; Yong-Zhi Tan; Jie Wang; Yi-Lu Shao; Qian-Wang Zheng; Yuan Zou; Jun-Fang Lin; Mou-Tong Chen; Zhi-Wei Ye (Food Bioscience, 2025)

Evaluation of a tilapia epitopes vaccine against Streptococcus agalactiae based on phage display technology - Jun-Jie Sheng; Xue-Feng Wei; Mao-Lin Liu; Xiao-Hang Ren; Ming-Zhu Liu; Bin Zhu (Fish & Shellfish Immunology, 2025)

Seismic performance of a low yield point steel link with corrugated web for RC double-column bridge bent - Sidong Feng; Jun He; Wei Fan; Weiwei Lin; George Vasdravellis (Engineering Structures, 2025)

Deep learning-assisted bionic gustatory sensing system based on aggregate-tuned silver nanoclusters and functionalized MXene for multiple foodborne pathogens recognition - Yuandong Lin; Wei Xiang; Fengqi Wang; Yong-Guang Jia; Jingzhu Wu; Jun-Hu Cheng (Chemical Engineering Journal, 2025)

Ultrasensitive detection of tsRNA through a transcleavage cross-linking Cas13-Cas14a tool - Gaihua Cao; Qin Wen; Qin Liu; Wei Xu; Jun Rao; Lin Xia; Xi Zhang (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Integrative analysis of coral plasticity and adaptations reveals key proteins driving resilience to changes in ocean carbonate chemistry - Xiangcheng Yuan; Ellias Y. Feng; Jingtian Wang; Lei Jiang; Tao Yuan; Hui Huang; Weihua Zhou; Jack Chi-Ho Ip; Wei-Jun Cai; Senjie Lin (Marine Life Science & Technology, 2025)
Understanding how corals adapt to changes in seawater carbonate chemistry is crucial for developing effective coral conservation strategies. Research to date has mostly focused on short-term experiments, overlooking long-term evolutionary effects. Here, we investigated the link between short-term stress responses and long-term genetic adaptations in the coral species Porites pukoensis through experiments under varying CO 2 and alkalinity conditions. Our results showed that alkalinity enrichment significantly increased coral calcification rates by 35%-45% compared to high CO 2 treatment, highlighting the potential of alkalinity enrichment to mitigate acidification impacts. Corals modulated relative expression levels of basic and acidic proteins in response to changes in seawater carbonate chemistry in the stress experiments. Genomic data revealed that this mechanism has been evolutionarily fixed in various organisms adapting to seawater carbonate chemistry. Additionally, both experimental and genomic results showed that extracellular matrix proteins, like collagen with von Willebrand factor type A domain, were modified in response to distinct carbonate environments. Molecular dynamics simulations and in-vitro experiments demonstrated that the structural stability of these proteins contributes to coral resilience under acidified conditions. This study established an integrated framework combining stress experiments, multi-omics analyses, molecular simulations, and in-vitro validation to identify key proteins involved in coral adaptation to acidification.

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

A carrier-assisted strategy for accelerating aerobic granulation under low superficial gas velocity: Critical contributions of sediment biochar and camellia shell biochar carriers - Qingxia Lin; Chuxuan Song; Jun Li; Ziqiang Liu; Xue Hu; Rui Xue; Suiqin Yang; Yang Gao; Wei Zhang; Lean Zhou; Julong Sun; Jinting Wang; et al. (Environmental Research, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Interactive effects of heavy metals and soil conditioners on rhizodegradation of long-chain petroleum hydrocarbons in soils - Ebhohon Endurance Odion; Jiaojiao Ma; Lambert Brau; Jun Wei Lim; Chuxia Lin (Environmental Pollution, 2025)

A novel high selectivity, strong acid resistance and antifouling polyamide thin film composite nanofiltration membrane fabricated with 3,3′-diamine-Tröger's base - Liu-Yang Gong; Nian Zhang; Jun-Yan Yu; Yan-Nan Wu; Chen-Jie Wei; He-Lin Zhu; Xue-Li Cao; Li-Fen Liu (Desalination, 2025)

Interfacial electronic coupling phase transition engineering of cobalt-based heterostructures for promoting high-efficiency electromagnetic absorption response - Jun Zhou; Xiaohang Ma; Lin Wang; Ying Meng; Shibin Lu; Zhenfa Zi; Wei Jiang (Chemical Engineering Journal, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Internally coupled concave nanobox@quantum dots nanoassemblies for SERS/fluorescence/colorimetric trimodal detection of prognostic biomarker in acute ischemic stroke - Wei-Bin Wang; Jian-Jun Li; Lin-Lin Fan; Jing-Yuan Wang; Guo-Jun Weng; Jian Zhu; Jun-Wu Zhao (Chemical Engineering Journal, 2025)

Suppression of OTUD4 protects against myocardial ischemia-reperfusion injury by increasing autophagic flux and inhibiting apoptosis in cardiomyocytes - Xin-xin Sun; Lin Qi; Ming-jun Dai; Fang-lin Lu; Yi-min Xiao; Wei-jin Sun; Yu Zhuang (Journal of Molecular Medicine, 2025)

Development of the immunopharmacognostic interventions on potentiating tumor recognition against prostate cancer - Tzu-Ting Su; Jun-Wei Lin; Shen-Chieh Wang; Tai-Yang Chen; Ju-I Chana; Pei-Wen Hsiaa; Hui-Ming Chen (Phytochemistry Letters, 2025)

Subtropical EM- surpass AM-dominated forests in increasing soil inorganic nitrogen availability: Evidence from a controlled field experiment - Yiting Qiu; Hang-Wei Hu; Hao Yang; Xiaoyu Chen; Jiamian Shi; Guigang Lin; Liuming Yang; Shengsheng Jin; Guangshui Chen; Jun-Tao Wang; Zhiqun Huang; Ji-Zheng He; et al. (Pedobiologia, 2025)

Microwave-converted insect frass biochar as a high-performance anode for crude glycerol-powered microbial fuel cells - Shu-Hui Liu; Wei-Jun Lai; Chi-Wen Lin; Hui Suan Ng (Journal of Water Process Engineering, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Sustained moderate oxidation system driven by gas-liquid-solid microenvironment under Mn(VII)-Fe(III)/sodium percarbonate (SPC) treatment: Mechanism and application in sludge dewatering - Wei Lin; Chuangxin Gong; Xiuxiang Ding; Xu He; Jun Ma; Mohamed E.A. Ali; Ahmed Shahat; Piotr Oleskowicz-Popiel; An Ding (Journal of Environmental Chemical Engineering, 2025)

Microwave-extracted insect melanin as a metal chelator for bimetallic bioelectro-fenton cathodes: A sustainable approach to ibuprofen-contaminated wastewater treatment - Shu-Hui Liu; Hui-Yu Tang; Chi-Wen Lin; Wei-Jun Lai (Chemical Engineering Journal, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Contrasting impacts of grassland restoration methods on soil greenhouse gases emissions under warming conditions in Northern Tibet - Hao Shi; Fei Xia; Lin-ling Ran; Hao-yang Wu; Jun-qiang Wang; Yun-yin Xue; Wei Wei; Shai-kun Zheng; Shuang Yan; Cai-hong Yang; Yu Zhang; Xiao-qin Qiu (CATENA, 2025)

A Typical Riedel Shear Pattern of Active Faults in the Laolongwan Basin, Northeastern Tibetan Plateau - Kai-Xun Wang; Xiao-Gang Li; Wei Shi; Xiang-You Feng; Qian Yang; Jie Li; Zheng-Jian Xu; Zhou-Jun Peng; Shao-Hua Xu; Yi-Xue Xiong; Mao Lin (Journal of Earth Science, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

River inflow and seawater intrusion shape distinct phytoplankton communities in jinghai bay, a coastal bay of the Yellow Sea - Jinchang Sui; Dongsheng Ding; Yan Zhang; Lin Zhu; Zhengguo Cui; Jun Sun; Yuqiu Wei (Marine Environmental Research, 2025)

Aggregation pheromones of Bostrichidae: A review - Li Yu; Xiao-Lu Cao; Wei Zheng; Jun Li; Fa-Yang Xie; Xia-Lin Zheng (Journal of Stored Products Research, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Toward more accurate quantification: A review of global large river basin management policies - Yi-Lin Zhao; Han-Jun Sun; Jie Ding; Zhen Hong; Ji-Wei Pang; Guene L. Razack; Nan-Qi Ren; Shan-Shan Yang (Journal of Environmental Management, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

High-efficiency blue fluorescent OLEDs enabled by a cost-effective blade-coated planar source evaporation strategy - Wan-Zhen Fo; Jun Li; Zhi-Lin Zhang; Bin Wei; Qisheng Zhang (Chemical Engineering Journal, 2025)

Synergistic enhancement of wetland purification performance by introducing intermittent aeration and zero-valent iron under chilling stress - Lin-Yuan Wu; Bing-Xu Guo; Ke-Jia Zhang; Jun-Yu Ai; Wei-Yi Shi; Qing-Yuan Tian; Wen-Huai Wang; Jun-Feng Li (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Properties of rich-Nae effect and reversible oxygen redox with a complete solid-solution sodium-storage behavior - Wei Zhao; Shao-Hua Luo; Yicheng Lin; Guodong Hao; Rui Huang; Pengyu Li; Ge Wang; Jun Cong; Shengxun Yan; Lixiong Qian (Chemical Engineering Journal, 2025)

Enhancing high-temperature phase stability and thermal properties of 5RE(TaxNb1-x)O4 high-entropy ceramics through chemical bonding strength optimization - Mengdi Gan; Liping Lai; Xiaoyu Chong; Qianqian Jin; Wei Yu; Jiankun Wang; Jun Wang; Lin Chen; Jingjin He; Jing Feng (Chemical Engineering Journal, 2025)

Boron isotope evidence for Ordovician-Silurian Transition postglacial marginal marine salinity with implications for redox conditions and biotic recovery - Jingyu Zhang; Wei Wei; Jun Shen; Jingbo Nan; Yi Zhong; Xiaojie Fan; Yanan Zhang; Qingsong Liu; Lin Chen; Leslie J. Robbins; Kurt O. Konhauser (Chemical Geology, 2025)

Metallothioneins protect against isoconazole nitrate-induced antitumor activity through the maintenance of cellular redox homeostasis in hepatocellular carcinoma - Chun-fen Mo; Ya-ruo Lei; Jun Lin; Yi Liu; Zhi-wei Zhao; Wen-jing Xiao; Wen-bai Yan; Wei-wei Zhang (Chemico-Biological Interactions, 2025)

Evaluation of pull-out behavior of headed stud connectors under freeze-thaw cycles: Experimental and numerical studies - Xing Wei; Gang Yang; Jun Chen; Lin Xiao; Zhirui Kang; Yingliang Wang (Cold Regions Science and Technology, 2025)

A practice guideline for therapeutic drug monitoring of mycophenolic acid for solid organ transplants - Shuang Liu; Hongsheng Chen; Zaiwei Song; Qi Guo; Xianglin Zhang; Bingyi Shi; Suodi Zhai; Lingli Zhang; Liyan Miao; Liyan Cui; Xiao Chen; Yalin Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2025)
Mycophenolic acid (MPA), the active moiety of both mycophenolate mofetil (MMF) and enteric-coated mycophenolate sodium (EC-MPS), serves as a primary immunosuppressant for maintaining solid organ transplants. Therapeutic drug monitoring (TDM) enhances treatment outcomes through tailored approaches. This study aimed to develop an evidence-based guideline for MPA TDM, facilitating its rational application in clinical settings. The guideline plan was drawn from the Institute of Medicine and World Health Organization (WHO) guidelines. Using the Delphi method, clinical questions and outcome indicators were generated. Systematic reviews, Grading of Recommendations Assessment, Development, and Evaluation (GRADE) evidence quality evaluations, expert opinions, and patient values guided evidence-based suggestions for the guideline. External reviews further refined the recommendations. The guideline for the TDM of MPA (IPGRP-2020CN099) consists of four sections and 16 recommendations encompassing target populations, monitoring strategies, dosage regimens, and influencing factors. High-risk populations, timing of TDM, area under the curve (AUC) versus trough concentration ( C 0 ), target concentration ranges, monitoring frequency, and analytical methods are addressed. Formulation-specific recommendations, initial dosage regimens, populations with unique considerations, pharmacokinetic-informed dosing, body weight factors, pharmacogenetics, and drug–drug interactions are covered. The evidence-based guideline offers a comprehensive recommendation for solid organ transplant recipients undergoing MPA therapy, promoting standardization of MPA TDM, and enhancing treatment efficacy and safety.

Unprecedented triterpenes with anti-inflammatory activity from Limax maximus - Ya-feng Wang; Pei-de Tang; Rui-jie He; Zhang-bin Liu; Yong-qiong Wei; Jun Ruan; Bing-yuan Yang; Yong-lin Huang (Journal of Natural Medicines, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Lignicolous freshwater fungi from karst landforms in China: Introducing Wongia guttulata sp. nov. associated with bamboo - Wen-Peng Wang; Hong-Wei Shen; Xi-Jun Su; Lin Yang; Zhong-Yuan Zhang; Zong-Long Luo (Mycological Progress, 2025)

Two new chemical constituents from the aerial parts of Tripterygium wilfordii - Xia Zhang; Lei Huang; Yu-Jun Tang; Ya-Lin Hu; Wei Xu; Hong-Yu Li; Yu-Bo Zhang; Xiao-Qi Zhang; Guang-Xiong Zhou (Natural Product Research, 2025)

Develop intelligent waste bin prototype based on fusion feature recognition of sounds and RGB images - Wei-Chun Chen; Chieh-Feng Chiang; Yu-Hao Lin; Hao-Jun Hsieh (Waste Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Mechanochemical degradation of UV-328 by solid oxidative reagents: Peroxydisulfate vs. peroxymonosulfate - Xiwang Zhao; Xitao Liu; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang (Journal of Hazardous Materials, 2025)

Dietary vitamin C improves muscle hardness and springiness associated with collagen and elastin synthesis in grass carp (Ctenopharyngodon idella) - Xin-Lei Xue; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Yang Liu; Yao-Bin Ma; Jun Jiang; Dong Han; Wen-Bin Zhang; Wei-Dan Jiang (Food Research International, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Hypertums A−J, bioactive polycyclic polyprenylated acylphloroglucinols with diverse skeletons from Hypericum perforatum L. (St. John's wort) - Wu-Yang Liu; Lin-Lin Gao; Wei Zhou; Yu-Na Ma; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Flexural behavior of reinforced concrete beams subjected to natural corrosion in marine environment - Yang Liu; Wei-Ping Zhang; Chao Jiang; Feng Wu; Jun-Li Qiu; Rui-Lin Wang; Nai-Hao Zheng (Engineering Structures, 2025)

CRISPR/Cas9-mediated genome editing in Ganoderma lucidum: recent advances and biotechnological opportunities - Dongmei Lv; Yan Xu; Zi-Xu Wang; Qi-Lin Zhang; Jin-Ping Yan; Jun-Wei Xu (World Journal of Microbiology and Biotechnology, 2025)

A century of advances in molecular genetics and breeding for sustainable resistance to rice blast disease - Xilai Huang; Wei Yao; Qianru Chen; Jinjun Lin; Jun Huang; Yuying Zou; Chenglong Guo; Bei He; Xiao Yuan; Chengyang Xu; Xionglun Liu; Yinghui Xiao; et al. (Theoretical and Applied Genetics, 2025)

Infrared Laser Stimulation of Purkinje Cells Primarily Depends on TRP Channel Activation - Bin-Bin Dong; Chen Wang; Wan-Qi Huang; Yu-Peng Bian; Jun Liu; Wei Chen; Lin Zhou; Ying Shen; Luxi Wang (Neuroscience Bulletin, 2025)

Identification of Mood Disorders Causal Genes by Integrating the Brain Proteome and Transcriptome - Rong-kun Zhu; Hong-jian Zhou; Jun Shi; Ling Ge; Yi Lin; Wen-hao Yin; Hui Zeng; Xiong-wei Wang (Molecular Neurobiology, 2025)

A Novel Metric for Assessing Long-Term Outcomes in Adults with Chiari Malformation Type I: Occipitocervical Dura Angulation (ODA)—Applications and Value - Bo Wang; Shi-Chao Chen; Yao-Wu Zhang; Wei-Hao Liu; Chong Wang; Yi-Xiang Liu; Guang-Hao Zheng; Jia-Lin Li; Kai Ji; Jun Yang; Yong-Zhi Wang; Wen-Qing Jia (The Cerebellum, 2025)

Significance of temperature and salinity in the dynamics of diatoms and dinoflagellates along the coastal Yellow Sea - Chenshi Weng; Dongsheng Ding; Qian Yang; Lin Zhu; Jun Sun; Keming Qu; Zhengguo Cui; Yuqiu Wei (Progress in Oceanography, 2025)

Impact on nonlinear runoff of LID facilities and parameter response in the TVGM model - Pengjun Li; Luwen Zhuang; Kairong Lin; Dunxian She; Qiang Wang; Wei Luo; Jianliang He; Jun Xia (Journal of Hydrology, 2025)

Differential magmatism and tectonic evolution during the rift stage within the Baiyun Sag of the Pearl River Mouth Basin in the northern South China Sea - Bo Yan; Xuan-Long Shan; Zhe Wei; Guo-Li Hao; Peng-Lin Zhang; Ling Ma; Zhi-Hao Wang; Pu-Jun Wang; N.G. Boriskina (Gondwana Research, 2025)

Characterization of GR-14 peptide from Cordyceps militaris mycelial albumin and its mechanism of heat protection on Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Zhi-Wei Ye; Li-Qiong Guo; Yuan Zou; Jun-Fang Lin (Food Bioscience, 2025)

Dietary AiiO-AIO6 mitigated Aeromonas hydrophila-induced intestinal inflammation in juvenile grass carp (Ctenopharyngodon idella) involving in NF-κB signaling and pyroptosis - Jie Huang; Lin Feng; Wei-Dan Jiang; Yang Liu; Jun Jiang; Hong-Mei Ren; Chai-Mei Wu; Xiao-Qiu Zhou; Pei Wu (Fish & Shellfish Immunology, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Atmospheric CO2 and CH4 observations in Hangzhou before, during, and after the 2023 Asian Games: Insights from vehicle-carried and fixed stations - Tianhao Wang; Jiansen Wang; Ning Hu; Ruonan Li; Meng Shan; Qun Lin; Longlong Chen; Jun Wang; Yuxin Jiang; Zhonghao Yang; Wei Xiao (Atmospheric Pollution Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Overview and Prospect of Data Assimilation in Numerical Weather Prediction - Lili Lei; Fuzhong Weng; Wansuo Duan; Yaodeng Chen; Lin Zhang; Ruichun Wang; Jun Yang; Xiaohao Qin; Wei Han; Jun Li; Jinzhong Min; Zhifang Xu; et al. (Journal of Meteorological Research, 2025)

Potential links between the progress in environmental governance and the prevalence of mental disorder burden: New insight from a dynamic panel-data analysis for 197 countries - Jun-Yan Xi; Li-Chang Chen; Xue-Qi Li; Jie Hu; Wei Hu; Jian-Jun Bai; Yi-Ning Xiang; Yu-Can Zhang; Jia-Jia Wang; Shi-Hao Wang; Jing Gu; Yuan-Tao Hao; et al. (Sustainable Cities and Society, 2025)

Effect of bromide ion on the formation and toxicity of halonitromethanes from Microcystis aeruginosa solution during UV/chloramine disinfection - Qi Xue; Qian Tang; Lin Deng; Wei Luo; Mingle Xia; Shuang Fu; Chaoqun Tan; Jun Hu; Rajendra Prasad Singh (Journal of Water Process Engineering, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Endophytic fungi promote peanut fitness by re-establishing rhizosphere nematode communities under continuous monocropping conditions - Xiang-Yu Zhang; Hao-Ran Li; Hui-Jun Jiang; Xiao-Han Wu; Chen-Yu Ma; De-Lin Luo; Wei Zhang; Chuan-Chao Dai (Plant and Soil, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Spatial metabolomics and feature-based molecular networking to unveiling in-situ quality markers landscape and reflecting geographic origins of pomegranate seeds - Yuye Gao; Tian Tian; Xiaojing Liu; Yi Zhang; Ping Hai; Wei Zhang; Yujia Zhai; Chen Wang; Jian-lin Wu; Jun Wen; Tingting Zhou (Food Chemistry, 2025)

Response surface methodology and Box-Behnken design optimization of Sulfaquinoxaline removal efficiency and degradation mechanisms by Bacillus sp. strain DLY-11 - Chunyan Chen; Zifeng Luo; Hongxing Tu; Xiaojun Lin; Yuwan Pang; Jianfeng Huang; Jun Zhang; Xiujuan Wang; Qianyi Cai; Zebin Wei; Jingwen Zeng; Jinrong Qiu (Journal of Hazardous Materials, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Tillage effects on maize yield, N use efficiency and GHG emissions under parallel N application in Northwest China - Hao-yang Wu; Lin-ling Ran; Jun-qiang Wang; Shuang Yan; Yun-yin Xue; Fei Xia; Hao Shi; Wei Wei; Yu Zhang; Shai-kun Zheng (Field Crops Research, 2025)

Experimental investigation on swelling and gas breakthrough properties of GMZ bentonite considering alkaline solution effects - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Bao Chen; Yu-Jun Cui (Engineering Geology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced synergistic effect of acidity and active phase for Ni-Co@NHZ-5-AT on hydroconversion of benzyoxybenzene to polycyclic alkanes - Xiao-Wei Yu; Yan-Jun Li; Yu-Hong Kang; Juan Gao; Pei-Lin Yang; Guang-Hui Liu; Shou-Long Gong; Xiao-Yu Kang; Yong Gao; Xian-Yong Wei; Wei Lu (Biomass and Bioenergy, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Combination mechanism and dimethyl ether removal performance of organic-bound water in kitchen waste - Jipeng Sun; Wei Zhu; Jun Zhong; Biao Mu; Xin Wang; Xinyi Wang; Yucheng Xu; Jun Cao; Naixi Lin (Waste Management, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Improved soil organic matter monitoring by using cumulative crop residue indices derived from time-series remote sensing images in the central black soil region of China - Mei-Wei Zhang; Xiao-Lin Sun; Mei-Nan Zhang; Hao-Xuan Yang; Huan-Jun Liu; Hou-Xuan Li (Soil and Tillage Research, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Moxifloxacin plus Cordyceps polysaccharide ameliorate intestinal barrier damage due to abdominal infection via anti-inflammation and immune regulation under simulated microgravity - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Bing-Xin Xu; Hong-Wei Sun; Jian-Wu Yang; Shao-Yan Si; et al. (Life Sciences in Space Research, 2025)

A novel electrochemical sensor based on La-MOF@C60-β-cyclodextrin composite for sensitive detection of dichlorophen in lake and tap water - Yu Xie; Wei Zhou; Jia-Wen Yin; Yi Li; Lin-Li Hou; Li-Min Liu; Li-Jun Liu; Kalle Salminen; Jian-Jun Sun (Journal of Environmental Chemical Engineering, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Effects of reclamation on the distribution and diversity of comammox along the coastal wetlands of China - Dongyao Sun; Yinghui Jiang; Hengchen Wei; Jun Li; Dengzhou Gao; Xianbiao Lin; Cheng Chen; Guoyu Yin; Yifei Zhang; Lijun Hou; Min Liu; Ping Han (International Biodeterioration & Biodegradation, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

The Jinchang deposit, Ailaoshan Belt: overprint of Miocene orogenic gold mineralization on Triassic hydrothermal nickel sulfide mineralization - Huajian Li; Qingfei Wang; David Groves; Chaoyi Dong; Weijun Weng; Wei Ma; Lin Yang; Ziqing Zhu; Jun Deng (Mineralium Deposita, 2025)

The beneficial potential of protein hydrolysates as prebiotic for probiotics and its biological activity: a review - Ping-Ping Gao; Han-Qing Liu; Zhi-Wei Ye; Qian-Wang Zheng; Yuan Zou; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Critical Reviews in Food Science and Nutrition, 2024)

Estimation of suspected estrogenic transformation products generated during preservative butylparaben chlorination using a simplified effect-based analysis approach - Jie Ouyang; Min Lin; Fang Wei; Chen Ling; Tingyu Lu; Yao Liu; Beimeng Qi; Jun Hu; Jian He; Guoqiang Zhuang (Water Research, 2024)

A comprehensive review of microplastic aging: Laboratory simulations, physicochemical properties, adsorption mechanisms, and environmental impacts - Yu Gao; Wei Gao; Yuzhi Liu; Donglei Zou; Yuan Li; Yingzi Lin; Jun Zhao (Science of The Total Environment, 2024)

Nitrogen fixation of different seasons and parts of seagrass Enhalus acoroides in Xincun Bay, northern South China Sea - Zhen-Zhen Wu; Xiao-Mei Li; Hui Zhao; Long Wei; Jun-De Dong; Mei-Lin Wu (Regional Studies in Marine Science, 2024)

A TT1–SCE1 module integrates ubiquitination and SUMOylation to regulate heat tolerance in rice - Hong-Xiao Yu; Ying-Jie Cao; Yi-Bing Yang; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Huai-Yu Zhao; Zi-Qi Lu; Shuang-Qin Guo; Jie-Jie Lei; Ben Liao; et al. (Molecular Plant, 2024)

Toxic effects of microplastics (MPs) on aquatic plants and phytoremediation potential in freshwater environments - Xingrong Yao; Zuojiang Lin; Wei Chen; Zhengwei Pan; Liangang Hou; Jun Li; Dongyue Li; Wanqi Liu; Kaiyao Hu (Journal of Water Process Engineering, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

The impact of cooking methods on the physical, sensory, and nutritional quality of fish - Sook Chin Chew; Yu Hsuan How; Lee Sin Chang; Choon Hui Tan; Kalvin Meng Jun Chuo; Stephenie Yoke Wei Wong; Pascal Degraeve; Kar Lin Nyam (International Journal of Gastronomy and Food Science, 2024)

Deep insights into the assembly mechanisms, co-occurrence patterns, and functional roles of microbial community in wastewater treatment plants - Zi-Yan Wei; Min Feng; Ding-Xi Zhang; Cheng-Ying Jiang; Ye Deng; Zhu-Jun Wang; Kai Feng; Yang Song; Nan Zhou; Yu-Lin Wang; Shuang-Jiang Liu (Environmental Research, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Transcriptome profiling of longissimus dorsi during different prenatal stages to identify genes involved in intramuscular fat deposition in lean and obese pig breeds - Jun Feng Chen; Jing Wang; Jin Chai; Wei Jin; Qiao Ling Ren; Qiang Ma; Qing Xia Lu; Jia Jie Sun; De Lin Mo; Jia Qing Zhang; Bao Song Xing (Molecular Biology Reports, 2024)
Background There was significant difference in muscle development between fat-type and lean-type pig breeds. Methods and results In current study, transcriptome analysis and bioinformatics analysis were used to compare the difference in longissimus dorsi (LD) muscle at three time-points (38 days post coitus (dpc), 58 dpc, and 78 dpc ) between Huainan (HN) and Large white (LW) pig breeds. A total of 24500 transcripts were obtained in 18 samples, and 2319, 2799, and 3713 differently expressed genes (DEGs) were identified between these two breeds at 38 dpc, 58 dpc, and 78 dpc, respectively. And the number and foldchange of DEGs were increased, the alternative splice also increased. The cluster analysis of DEGs indicated the embryonic development progress of LD muscle between these two breeds was different. There were 539 shared DEGs between HN and LW at three stages, and the top-shared DEGs were associated with muscle development and lipid deposition, such as KLF4, NR4A1, HSP70, ZBTB16 and so on. Conclusions The results showed DEGs between Huainan (HN) and Large white (LW) pig breeds, and contributed to the understanding the muscle development difference between HN and LW, and provided basic materials for improvement of meat quality.

Integrated analysis of methylation and transcriptome identifies a novel risk model for diagnosis, prognosis, and immune characteristics in head and neck squamous cell carcinoma - Jun-wei Zhang; Xi-Lin Gao; Sheng Li; Shuang-hao Zhuang; Qi-Wei Liang (Molecular Genetics and Genomics, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Effects of dietary vitamin D3 and carbohydrate levels on growth performance, carbohydrate metabolism, and intestinal health of yellow catfish (Pelteobagrus fulvidraco) - Li-Xiang Wu; Qing-Lin Li; Zhi Luo; Mette Sorensen; Xiao-Lei Wei; Hua-Jun Zhang; Xiao-Ying Tan (Aquaculture, 2024)

Mitigating soil nitrification and greenhouse gas emissions in non-paddy cropping systems by micro-molar hydrogen peroxide - Kaiqing Fan; Udara Piyathilake; Yunji Wang; Jun Wei Lim; Chuxia Lin; Junhao Qin; Rongliang Qiu (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Bi-functional NiFe2O4/SrTiO3 S-scheme heterojunction for eminent performance photocatalytic treatment of sewage effluent and electrochemical hydrazine determination - Sze-Mun Lam; Sin-May Wong; Jin-Chung Sin; Honghu Zeng; Haixiang Li; Liangliang Huang; Hua Lin; Abdul Rahman Mohamed; Jun-Wei Lim; Zuzeng Qin (Environmental Research, 2024)

A three-stage oxidation method improves sludge dewaterability by achieving sustained oxidation and phased enhanced coagulation: Ingeniously using H2O2 as a “converter” - Wei Lin; An Ding; Chuangxin Gong; Xiuxiang Ding; Peter Desmond; Piotr Oleskowicz-Popiel; Xu He; Jun Ma; Huu Hao Ngo (Chemical Engineering Journal, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p

Integrated induction of silver resistance determinants and production of extracellular polymeric substances in Cupriavidus metallidurans BS1 in response to silver ions and silver nanoparticles - Jia-Xin Dai; Yanshuang Yu; Le-Xing You; Hong-Lin Zhong; Yuan-Ping Li; Ai-Jun Wang; Jon Chorover; Ren-Wei Feng; Hend A. Alwathnani; Martin Herzberg; Christopher Rensing (Chemosphere, 2024)

Hotspot–subduction zone interactions and their resource effects at ∼120 Ma on the central Tibetan Plateau - Jia-Wei Bai; Jian-Jun Fan; Ye Zhan; Bo-Chuan Zhang; Si-Lin Sun; Yu-Jie Hao (Lithos, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Rainwater-borne H2O2 accelerates roxarsone degradation and reduces bioavailability of arsenic in paddy rice soils - Kaiqing Fan; Liji Chen; Huashou Li; Jun Wei Lim; Chuxia Lin; Junhao Qin; Rongliang Qiu (Journal of Hazardous Materials, 2024)

High-performance solar water purification enabled by controlled water convection in integrated porous aerogel multistage distiller - Chengcheng Li; Zhen Li; Peng Zhu; Weihua Mao; Yecheng Wang; Shishi Lin; Yang Cao; Jun Liu; Mingxin Zhang; Shuyi Huang; Wei Huang (Chemical Engineering Journal, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

First identification of Carboniferous mafic dikes during a period of arc magmatic quiescence in the Northern Qiangtang terrane, central Tibet: Back-arc extension and implications for opening of the Xijir Ulan Ocean - Zhi-Wei Yu; Wei Dan; Qiang Wang; Xiu-Zheng Zhang; Jun Wang; Bing Chen; Lin Gong (Lithos, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Signal Transduction Associated with Mn-induced Neurological Dysfunction - Xiao-wei Zheng; Yuan-yuan Fang; Jun-jie Lin; Jing-jing Luo; Shao-jun Li; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Production of cleavage-resistant phytase transgenic pigs by handmade cloning - Mingyuan Zhang; Jun Zhang; Haowen Yang; Shijin Chen; Xiaoliang Chen; Yuemeng Huang; Baojian Chen; Yanjun Wu; Qinyang Jiang; Yafen Guo; Yingming Wei; Xiukun Lin; et al. (Theriogenology, 2024)

A hybrid algorithm based on the proposed square strategy and NSGA-II for ship pipe route design - Wei-qiang Yan; Ming-jun Yang; Yan Lin (Ocean Engineering, 2024)

Amphichdiral enhancement on singlet oxygen generation and stable thallium immobilization using iron-driven copper oxide - Zhujun Liu; Xinning Dai; Jun He; Mengyi Lin; Hongbing Luo; Liangqian Fan; Ke Zhang; Dandan Ma; Jun Wang; Wei Chen (Journal of Environmental Management, 2024)

Potential of Cordyceps militaris protein hydrolysates as prebiotic and thermo-protectants of Lactobacillus fermentum J26 - Ping-Ping Gao; Han-Qing Liu; Qian-Wang Zheng; Yuan Zou; Zhi-Wei Ye; Tao Wei; Li-Qiong Guo; Jun-Fang Lin (Food Bioscience, 2024)

Analysis of proteomics and in silico allergenicity prediction of soluble proteins in selenium-enriched peanut leaves - Qi Gao; Wei-Xuan Li; Zi-Heng Liu; Mei Tie; Xue-Jun Gu; Masaru Tanokura; You-Lin Xue (Food and Bioproducts Processing, 2024)

Zero-strain Co-doped Na2FeP2O7/carbon delivers superior rate capability and long-cycle stability for sodium ion batteries - Jianhong Gao; Ziwei Chen; Wei Cao; Jiale Chen; Ming Zhang; Feng Lin; Yongsheng Li; Waqar Ahmad; Min Ling; Chengdu Liang; Jun Chen (Chemical Engineering Journal, 2024)

Binary-Network structured PI@SiO2 nanofibrous composite aerogels with temperature invariant superelasticity for thermal insulation - Qicheng Xue; Nanxi Dong; Peiqi Fan; Daolei Lin; Guofeng Tian; Jun Liu; Jiaming Wei; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2024)

Inhibition of ER stress using tauroursodeoxycholic acid rescues obesity-evoked cardiac remodeling and contractile anomalies through regulation of ferroptosis - Feng-Juan Li; Miyesaier Abudureyimu; Zeng-Hui Zhang; Jun Tao; Asli F. Ceylan; Jie Lin; Wei Yu; Russel J. Reiter; Milad Ashrafizadeh; Jun Guo; Jun Ren (Chemico-Biological Interactions, 2024)

Acupoint catgut embedding attenuates oxidative stress and cognitive impairment in chronic cerebral ischemia by inhibiting the Ang II/AT1R/NOX axis - Jurui Wei; Qi Ai; Peier Lv; Wenyao Fang; Zixuan Wang; Jiumei Zhao; Wenqing Xu; Lin Chen; Jun Dong; Bijun Luo (Pflügers Archiv - European Journal of Physiology, 2024)

Upregulation of hsa-miR-141-3p promotes uterine cervical carcinoma progression via targeting dual-specificity protein phosphatase 1 - Zi-Qian Liang; Wei Zhang; Da-Tong Zeng; Jun-Hong Chen; Jia-Yuan Luo; Lin Shi; Kang-Lai Wei; Gang Chen (Functional & Integrative Genomics, 2024)

Rederiving kinetics to model biohydrogen production from immobilized microalgae alginate beads at various polymerization degrees of alginate under dark fermentative environment - Jia Min Woon; Kuan Shiong Khoo; Nurul Tasnim Sahrin; Fatima Musa Ardo; Jun Wei Lim; Woei-Yenn Tong; Yi Jing Chan; Chuxia Lin; Pei Sean Goh; Sabah Ansar; Man Kee Lam (Algal Research, 2024)

Correction: Indoor air pollution by solid fuel usages for cooking is longitudinally associated with possible sarcopenia in middle-aged Chinese population - Guo Ming Su; Ke Xin Jia; Jun Yi Liu; Xu Chen; Yi Lin Shen; Jia Jing Cai; Qi Wei Guo; Jia Lin; Ding Zhi Fang (Journal of Environmental Health Science and Engineering, 2024)

Correlation between electricity generation of piezoelectric ceramics and cyclic behavior of UGMs under traffic loading - Chuan Gu; Guanyu Zhang; Jun Wang; Yuanqiang Cai; Wei Hu; Xiangxing Lin (Soil Dynamics and Earthquake Engineering, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

Plant regeneration in the new era: from molecular mechanisms to biotechnology applications - Chunli Chen; Yuxin Hu; Momoko Ikeuchi; Yuling Jiao; Kalika Prasad; Ying Hua Su; Jun Xiao; Lin Xu; Weibing Yang; Zhong Zhao; Wenkun Zhou; Yun Zhou; et al. (Science China Life Sciences, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Indoor air pollution by solid fuel usages for cooking is longitudinally associated with possible sarcopenia in middle-aged Chinese population - Guo Ming Su; Ke Xin Jia; Jun Yi Liu; Xu Chen; Yi Lin Shen; Jia Jing Cai; Qi Wei Guo; Jia Lin; Ding Zhi Fang (Journal of Environmental Health Science and Engineering, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Learning spatiotemporal dependencies using adaptive hierarchical graph convolutional neural network for air quality prediction - Wei Hu; Zhen Zhang; Shiqing Zhang; Caimei Chen; Jiwei Yuan; Jun Yao; Shuchang Zhao; Lin Guo (Journal of Cleaner Production, 2024)

Late Jurassic–Early Cretaceous Rebangco ophiolite, Tibet: Constraints on the Meso-Tethys Ocean tectonic evolution - Jia-Wei Bai; Jian-Jun Fan; Yu-Jie Hao; Bo-Chuan Zhang; Si-Lin Sun (Journal of Asian Earth Sciences, 2024)

All-natural plant-based HIPE-gels simultaneously stabilizing with Quillaja saponin and soy protein isolate: Influence of environmental stresses on stability - Xiao-Wei Chen; Tian-Ge Wang; Wen-Jun Yin; Lin-Shang Zhang; Shang-De Sun (Food Hydrocolloids, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Controlled solvothermal synthesis of self-assembled SrTiO3 microstructures for expeditious solar-driven photocatalysis dye effluents degradation - Khar-Lok Lim; Jin-Chung Sin; Sze-Mun Lam; Honghu Zeng; Hua Lin; Haixiang Li; Liangliang Huang; Jun-Wei Lim (Environmental Research, 2024)

Electrolyte design to regulate the electrode–electrolyte interface on the electrochemical performance for K0.5MnO2||graphite-based potassium-ion batteries - Yicheng Lin; Shaohua Luo; Pengwei Li; Jian Feng; Wei Zhao; Jun Cong; Shengxue Yan (Chemical Engineering Journal, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Marinobacter albus sp. nov., Isolated from Sand Sediment in a Coastal Intertidal Zone - Tai-Hang Deng; Yu Zhang; Wen-Wu Zhang; Yue Su; Jia-Wei Gao; Jun-Jie Ying; Lin Xu; Xiao-Ming Xia; Cong Sun (Current Microbiology, 2024)

Root rot induces a core assemblage of bacterial microbiome to prevent disease infection in Sanqi ginseng - Baoying Wang; Qing Xia; Yulan Lin; Fugang Wei; Shaozhou Yang; Chuanchao Dai; Xinqi Huang; Jinbo Zhang; Zucong Cai; Jun Zhao (Applied Soil Ecology, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

The effects of microgravity on stem cells and the new insights it brings to tissue engineering and regenerative medicine - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Hong-Feng Yan; Tao Zhang; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Sustained oxidation of Tea-Fe(III)/H2O2 simultaneously achieves sludge reduction and carbamazepine removal: The crucial role of EPS regulation - Wei Lin; Renglu Chen; Chuangxin Gong; Peter Desmond; Xu He; Jun Nan; Guibai Li; Jun Ma; An Ding; Huu Hao Ngo (Journal of Hazardous Materials, 2024)

Formation and toxicity alteration of halonitromethanes from Chlorella vulgaris during UV/chloramination process involving bromide ion - Qian Tang; Lin Deng; Yuyang Mao; Shuang Fu; Wei Luo; Tingting Huang; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Management, 2024)

Experimental study on propagation dynamics characteristic of premixed syngas/air explosion in parallel narrow channels - Pinkun Guo; Chuanqing Xu; Junchen Lu; Zhirong Wang; Xinyue Chang; Lin Hu; Zepeng Wang; Jun Dong; Wei Wang (Fuel, 2024)

From growth promotion to intestinal inflammation alleviation: Unraveling the potential role of Lactobacillus rhamnosus GCC-3 in juvenile grass carp (Ctenopharyngodon idella) - Zhen Chen; Lin Feng; Pei Wu; Wei-Dan Jiang; Jun Jiang; Xiao-Qiu Zhou; Yang Liu (Fish & Shellfish Immunology, 2024)

Impacts of large-scale suspended mussel farm on seston depletion - Wei Zhong; Jun Lin; Qingping Zou; Hidekatsu Yamazaki; Wei Yang; Guanlin Yang (Estuarine, Coastal and Shelf Science, 2024)

Machine learning assisted combined systems of wastewater treatment plants with constructed wetlands optimal decision-making - Wei Dai; Ji-Wei Pang; Ying-Jun Zhao; Jie Ding; Han-Jun Sun; Hai Cui; Hai-Rong Mi; Yi-Lin Zhao; Lu-Yan Zhang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Correction to: BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2024)

Flushing emissions of methane and carbon dioxide from mangrove soils during tidal cycles - Chiao-Wen Lin; Wei-Jen Lin; Chuan-Wen Ho; Yu-Chen Kao; Zhao-Jun Yong; Hsing-Juh Lin (Science of The Total Environment, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

Effect of an air bubble on the collapse shock wave of a cavitation bubble - Jian-Bo Li; Wei-Lin Xu; Yong Xia; Mao Ye; Yan-Wei Zhai; Jun Deng (Ocean Engineering, 2024)

Positive effects of biochar application and Rhizophagus irregularis inoculation on mycorrhizal colonization, rice seedlings and phosphorus cycling in paddy soils - Yixuan CHEN; Zhonghua WEN; Jun MENG; Zunqi LIU; Jialong WEI; Xiyu LIU; Ziyi GE; Wanning DAI; Li LIN; Wenfu CHEN (Pedosphere, 2024)

Efficient hydrogen recovery from wastewater treatment by piezo-photocatalytic heterostructure - Xinning Dai; Zhujun Liu; Zhihan Zhao; Jun Wang; Hongbing Luo; Lin Cheng; Wei Chen (Journal of Cleaner Production, 2024)

Degradation of chloroquine phosphate during UV/H2O2 process: Performance, kinetics, and degradation pathways - Haofeng Dai; Wei Luo; Lei Jin; Lin Deng; Qing Wang; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Chemical Engineering, 2024)

Whole-genome sequencing of Escherichia coli from retail meat in China reveals the dissemination of clinically important antimicrobial resistance genes - Qin Wang; Ying-Yue Han; Tie-Jun Zhang; Xuan Chen; Heng Lin; Hong-Ning Wang; Chang-Wei Lei (International Journal of Food Microbiology, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

The Pacific-North American teleconnection in the Cenozoic - Zhibo Li; Yongyun Hu; Jian Zhang; Xiang Li; Jiaqi Guo; Jiawenjing Lan; Qifan Lin; Shuai Yuan; Mengyu Wei; Zihan Yin; Qiang Wei; Xiujuan Bao; et al. (Global and Planetary Change, 2024)

Recent advances in liquid fuel production from plastic waste via pyrolysis: Emphasis on polyolefins and polystyrene - Soheil Valizadeh; Behzad Valizadeh; Myung Won Seo; Yong Jun Choi; Jechan Lee; Wei-Hsin Chen; Kun-Yi Andrew Lin; Young-Kwon Park (Environmental Research, 2024)

Triboelectric nanogenerator based on multi-component crosslinked network hydrogel for intelligent human motion sensing - Kang-Rui Zhu; Lin-Xin Wu; Meng-Nan Liu; Chang-Long Li; Wei-Zhi Song; Kong-Qiang Wei; Jun Zhang; Seeram Ramakrishna; Yun-Ze Long (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Risk level assessment of typhoon-induced wave fields around a large-scale suspended mussel farm - Yanjiao Li; Jun Lin; Wei Zhong; Sijian Wang; Long Li (Frontiers in Marine Science, 2024)
Suspended shellfish aquaculture, utilizing longlines and buoys fixed on the sea surface, is a crucial source of global seafood. However, typhoons, as the most common disasters in coastal regions, can generate massive waves and pose a threat to the safety of suspended aquaculture facilities. Therefore, it is essential to investigate the risk levels associated with suspended aquaculture farms during typhoon waves. The example of a large-scale suspended mussel farm in the East China sea was examined in this study. The wave conditions under extreme wind conditions (25m/s) and different typhoon paths were predicted using the SWAN model and modeled results compared well with the observed wave and wind data. The results indicated that when the center of the east-side typhoon was located at the same latitude as the farm, it will face the highest risk level. However, for the west-side and intermediate sweeping typhoons, the risk level reached highest in the farm, when the typhoon center is lower than the latitude of it. Under the combined effects of wind fetch and topography, the risk level in the southeast farming area of the island is the highest under different wind conditions. The farms to the northwest of the island face a higher risk level during the passage of east-side sweeping typhoons, while the southern farms of the island experience an elevated risk level during the west-side and intermediate sweeping typhoons. It is suggested that farming regions with lower risk levels are more conducive to the cultivation of species with longer culture cycles. Conversely, regions considered at higher risk are more suitable for species with shorter culture cycles. The study affords a reference for the optimization and insurance of suspended aquaculture farms.

Association between blood arsenic concentration and dyslipidemia: Mediating effect of lipid peroxidation in the elderly - Jia-Hui Huang; Yi Wu; Wei He; Jun-Xian Wang; Lin Fu; Xi Chen (Journal of Trace Elements in Medicine and Biology, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Functional connectivity disruption of insular subregions in the cirrhotic patients with minimal hepatic encephalopathy - Hong-Yu Lin; Hui-Wei Huang; Qiu-Yi Dong; Li-Min Cai; Hua-Jun Chen (Brain Imaging and Behavior, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Corrigendum to “Serviceability evaluation of highway tunnels based on data mining and machine learning: A case study of continental United States” [Tunnelling and Underground Space Technology 142 (2023) 105418] - Ya-Dong Xue; Wei Zhang; Yi-Lin Wang; Wei Luo; Fei Jia; Sheng-Teng Li; Hao-Jun Pang (Tunnelling and Underground Space Technology, 2024)

Assessing grassland cultural ecosystem services supply and demand for promoting the sustainable realization of grassland cultural values - Lan Wang; Lin Huang; Wei Cao; Jun Zhai; Jiangwen Fan (Science of The Total Environment, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Inhibitory mechanism of esculetin on tyrosinase and browning of fresh-cut apple: New perspectives - Lin-Jun Wang; Qiu-Han Bai; Qiu-Xia Pan; Yi-Feng Wu; Ting-Ting Shao; Yi-Wen Guo; Wen-Shuang Wei; Yi-Ting Wen; Wei-Ming Chai (Postharvest Biology and Technology, 2024)

Mitochondrial coding genes mediate insecticide tolerance in the oriental fruit fly, Bactrocera dorsalis (Hendel) - Shi-Die Jiang; Lei Wang; Lin Wang; Jun Sun; Jin-Jun Wang; Dan-Dan Wei (Pesticide Biochemistry and Physiology, 2024)

Simulated microgravity altered the gene expression profiles and inhibited the proliferation of Kupffer cells in the early phase by downregulating LMO2 and EZH2 - Jun Ge; Yuan Yue; Hong-Yun Nie; Kai-Ge Liu; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Incorporating photocatalytic fuel cell with dual S-scheme CuBi2O4/Bi2WO6/ZnO NRA photoanode for energy recuperation from municipal wastewater treatment under sunlight - Zi-Jun Yong; Sze-Mun Lam; Jin-Chung Sin; Abdul Rahman Mohamed; Honghu Zeng; Haixiang Li; Hua Lin; Liangliang Huang; Jun-Wei Lim (Journal of Environmental Chemical Engineering, 2024)

Estimates of chlorine isotope fractionation factors using density functional theory: Applications to ore-forming systems - Miao-Miao Zhang; Hai-Zhen Wei; Jian-Jun Lu; A.E. Williams-Jones; C.J. Eastoe; Wei-Qiang Li; Zhi-Guang Xia; S.V. Hohl; Jing Ma; Yue Cai; Shao-Yong Jiang; Jun-Lin Wang (Geochimica et Cosmochimica Acta, 2024)

Three new glycosides from the stems of Eurya chinensis R. Br - Hui-Jun Liang; Qian-Ran Li; Bai-Lin Li; Chen Ni; Wei-Jie Zhang; Yu-Wen Fan; Zhuo-Yi Ao; Juan-Juan Hu; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2024)

Exogenous stimulation-induced biosynthesis of volatile compounds: Aroma formation of oolong tea at postharvest stage - Lin Zeng; Shan Jin; Yan-Qun Xu; Daniel Granato; Yan-Qing Fu; Wei-Jiang Sun; Jun-Feng Yin; Yong-Quan Xu (Critical Reviews in Food Science and Nutrition, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Study on low methoxyl pectin (LMP) with varied molecular structures cross-linked with calcium inducing differences in the gel properties - Chun-lin Wu; Jun-ru Qi; Jin-song Liao; Zi-wei Liu; Chun-ai He (Food Hydrocolloids, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Eminent destruction of organics and pathogens concomitant with power generation in a visible light-responsive photocatalytic fuel cell with NiFe2O4/ZnO pine tree-like photoanode and CuO/Cu2O nanorod cathode - Sze-Mun Lam; Jin-Chung Sin; Meng Wei Warren Tong; Honghu Zeng; Haixaing Li; Liangliang Huang; Hua Lin; Jun-Wei Lim (Chemosphere, 2023)

Environmental forcing of phytoplankton carbon-to-diversity ratio and carbon-to-chlorophyll ratio: A case study in Jiaozhou Bay, the Yellow Sea - Yingzhe Wang; Zhengguo Cui; Dongsheng Ding; Qian Yang; Lin Zhu; Keming Qu; Jun Sun; Yuqiu Wei (Marine Pollution Bulletin, 2023)

Serviceability evaluation of highway tunnels based on data mining and machine learning: A case study of continental United States - Ya-Dong Xue; Wei Zhang; Yi-Lin Wang; Wei Luo; Fei Jia; Sheng-Teng Li; Hao-Jun Pang (Tunnelling and Underground Space Technology, 2023)

Overexpression of ABCB transporter genes confer multiple insecticide tolerances in Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) - Lin Wang; Shu-Hang Tian; Wei Zhao; Jin-Jun Wang; Dan-Dan Wei (Pesticide Biochemistry and Physiology, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Advanced dewatering of digested sludge through oxidative decomposition of humic substances: A comprehensive study - Yucheng Xu; Naixi Lin; Jun Zhong; Jipeng Sun; Guorui Li; Tao Sheng; Wei Zhu (Journal of Water Process Engineering, 2023)

Improved solid/liquid separation performance of hydrochar from sludge via hydrothermal carbonization - Jun Zhong; Wei Zhu; Biao Mu; Jipeng Sun; Xin Wang; Naixi Lin; Jun Cao (Journal of Environmental Management, 2023)

Non-targeted analysis and risk assessment of intentionally and non-intentionally added substances migrating from the emerging biodegradable food contact material poly(butylene adipate-co-terephthalate)/modified starch blend film - Jun Lin; Wei-Liang Wu; Ai-Hua Zhong; Yan-Ping Xian; Huai-Ning Zhong; Ben Dong; Ming Liang; Jun-Peng Hu; Yong-Ning Wu; Xing-Fen Yang; Hai-Xia Sui; Quan Zhou (Food Packaging and Shelf Life, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

Suppress moisture sensitivity of Ni-rich cathode materials by bioinspired self-assembly hydrophobic layer - Yingde Huang; Pei-Yao Li; Han-Xin Wei; Yu-Hong Luo; Lin-Bo Tang; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

Analysis of the driving factors of the change of erosion-deposition in the Minjiang Estuary, Southeast China - Xiaohe Lai; Jianping Jia; Yuebao Hou; Beihan Jiang; Chuan Lin; Xinlu Lin; Pu Xu; Cheng Chen; Jun Jiang; Yan Liu; Wen Wei (Frontiers in Marine Science, 2023)
Understanding the evolution and driving factors of sedimentation and erosion at the mouths of small and medium-sized mountain streams during various periods is essential for regional spatial utilization, development, and sustainable economic growth. This is particularly important when considering the combined impact of climate change and human activities. This paper presents an analysis of the changes in sedimentation and erosion of mouth isobaths and underwater deltas over different periods using nautical chart data (1950-2019) and analyzes the factors driving changes in sedimentation and erosion during different periods from 1950 to 2020 based on the runoff-sediment discharge of the Minjiang River (MR) and extreme climate factors such as typhoons, especially the driving factors that caused a sudden change in the sedimentation and erosion process between 1998 and 2005. The results indicate that runoff-sediment characteristics are crucial in driving sedimentation and erosion changes. In the past 70 years, the underwater delta of the MRE has mainly experienced four stages: deposition (1950-1992) -erosion (1993-1998) -deposition (1998-2011) -erosion (2011-2019). Taking the impoundment operation of the Shuikou Reservoir in 1993 as the node, the sediment load of the Minjiang River into the sea began to decrease sharply, and then the estuary quickly showed a state of erosion. The change of sediment flux into the sea is the main driving factor for the evolution of erosion and deposition in the Minjiang River Estuary (MRE). The critical value of the erosion-deposition transition is about 570.3 × 10 4 t/yr. After the estuary entered a state of erosion in 1993-1998, significant siltation suddenly occurred in 1998-2005. The reason for the siltation in this period may be related to the frequent transit typhoons and flood events in 1998-2005. Therefore, the change of river sediment supply into the sea is the main driving factor controlling the erosion and deposition evolution of the Minjiang River estuary on a long time scale of more than 10 years, which reflects the influence of large-scale human activities on the river and estuary area in the past half century. Extreme climate events are the incentive to adjust the estuary landform in the short term. Extreme climate events will not fundamentally change the process of estuarine geomorphological evolution under the background of sediment supply reduction.

Soil aggregate-associated organic carbon mineralization and its driving factors in rhizosphere soil - Jun-Ya Li; Peng Chen; Zhi-Guo Li; Lin-Yang Li; Run-Qin Zhang; Wei Hu; Yi Liu (Soil Biology and Biochemistry, 2023)

Propeller hydrodynamic excitation influenced by shafting whirling vibration considering different nonuniform inflow conditions: A numerical study - Chang-Lin Meng; Lie-Yi Dong; Dong-Hua Wang; Jia-Xuan He; Zhi-Jun Shuai; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Ocean Engineering, 2023)

General liquid vegetable oil structuring via high internal phase Pickering emulsion stabilized by soy protein isolate nanoparticles - Chenzhi Wang; Xin Guan; Jun Sang; Jiajing Zhou; Chunhua Wang; To Ngai; Wei Lin (Journal of Food Engineering, 2023)

Geology, fluid inclusions, and isotope signatures reveal hydrothermal evolution and genesis of the Aqishan Pb-Zn deposit in Eastern Tianshan and implications for exploration of skarn mineralization - Kang Wang; Shan-Yuan Lin; Yin-Hong Wang; Jia-Jun Liu; Fang-Fang Zhang; Wen-Xin Gu; Wei Zhang; Hui Zhang; Hao Zhang (Journal of Geochemical Exploration, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

Barium isotope fractionation during granitic magmatism and potential of δ138/134Ba for distinguishing magmatic-hydrothermal transition in granitic magma systems - Jun-Lin Wang; Hai-Zhen Wei; M.R. Palmer; A.E. Williams-Jones; Jing Ma; Shao-Yong Jiang; Simon V. Hohl; Yuan-Feng Zhu; Chun Huan; Miao-Miao Zhang; Jian-Jun Lu (Geochimica et Cosmochimica Acta, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Identification of circRNAs and circRNA-mRNA network of Epinephelus coioides during Singapore grouper iridovirus infection - Yi-Jie Cai; Wei Huang; Liang-Yuan Zhu; Yun-Xiang Lin; Cui-Fen Huang; Wen-Feng Yang; Jia-Lin Zhou; Jun-De Dong; Wei-Hua Zhou; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

In-situ utilization of EPS improves the directional oxidation ability of Fe(III)/H2O2 and enhances sludge dewaterability - Wei Lin; Chuangxin Gong; Renglu Chen; Xu He; Jun Nan; Guibai Li; Huu Hao Ngo; An Ding (Chemical Engineering Journal, 2023)

Characterization of Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov. and illumination of the distinct adaptative strategies of the genus Maribacter - Jia-Wei Gao; Jun-Jie Ying; Han Dong; Wen-Jia Liu; Dong-Yan He; Lin Xu; Cong Sun (Frontiers in Marine Science, 2023)
Polysaccharides are complex carbohydrates and are abundant in the marine environment. Microbes degrade and utilize them using Carbohydrate-active enzymes (CAZymes), which mediate polysaccharides into the marine carbon cycle. With the continued supply of polysaccharides from the marine environment, tidal flats are also abundant in polysaccharides, resulting in an abundance of marine polysaccharide degrading strains. In this study, three novel strains, designated as D37 T , M208 T , and SA7 T , were isolated from the intertidal sediment samples located in Zhoushan, Zhejiang and Huludao, Liaoning, PR China. The phylogenetic trees using the 16S rRNA gene and genome sequences showed that the three novel strains belonged to the genus Maribacter . The highest 16S rRNA gene sequence similarities between the three novel strains and other strains of the genus Maribacter were 98.7%, 99.2%, and 98.8%, respectively, while the ANI, AAI, and dDDH values between the three strains and the other strains of the genus Maribacter were 70-86%, 67-91%, and 17-30%, respectively, supporting their affiliation as novel species. Combined with other phenotypic and genotypic characterization in this study, three novel species are proposed as Maribacter polysaccharolyticus sp. nov., Maribacter huludaoensis sp. nov., and Maribacter zhoushanensis sp. nov., respectively, for the three strains. Furthermore, we compared all available genomes of Maribacter representatives and found that Maribacter strains could be divided into two groups (A and B). The two groups are different in genome size and G + C content and gene densities of CAZyme, peptidase, and sulfatase. Group A possesses more CAZymes which are related to degrading laminarin, fucoidan, mannan, xylose, and xylan. This result suggests that the two groups may have different niche adaptation strategies. Our study contributes to a better understanding of the role of marine flavobacteria in biogeochemical cycles and niche specialization.

Progress in biological activities and biosynthesis of edible fungi terpenoids - Hai-Ying Chen; Jin-Yu Lei; Shu-Li Li; Li-Qiong Guo; Jun-Fang Lin; Guang-Hong Wu; Jun Lu; Zhi-Wei Ye (Critical Reviews in Food Science and Nutrition, 2023)

Accumulation degree and risk assessment of metals in street dust from a developing city in Central Taiwan - Tser-Sheng Lin; Jun-Wei Wu; Thi-Dieu-Hien Vo; Van-Truc Nguyen; Yun-Ru Ju (Chemosphere, 2023)

Kinetic model derived from machine learning for accurate prediction of microalgal hydrogen production via conversion from low thermally pre-treated palm kernel expeller waste - Mohamad Zulfadhli Ahmad Sobri; Kuan Shiong Khoo; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sabah Ansar; Md Sohrab Hossain; Worapon Kiatkittipong; Chuxia Lin; Hui-Suan Ng; Juliana Zaini; Muhammad Roil Bilad; Man Kee Lam; et al. (Chemosphere, 2023)

Dietary selenium promoted muscle growth (myofiber hypertrophy rather than hyperplasia) by reducing endoplasmic reticulum stress in juvenile grass carp (Ctenopharyngodon idella) - Ya Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Jun Jiang; Jia-Yong Tang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Efficient activation of persulfate by metallic sulfide mineral for the efficient removal of pesticides: Performance, radical generation and mechanism - Xie Chen; Wen-Xuan Zhang; Zhi-Liang Chen; Xiao-Wen Yao; Man-Li Chen; Lin-Yin Tong; Wei Qian; Peng-Ran Guo; Ling-Jun Kong; Zeng-Hui Diao (Journal of Cleaner Production, 2023)

Degradation of metronidazole during the UV365-LED /chlorine process: Kinetics, influencing factors, and halonitromethanes formation - Wei Luo; Lin Deng; Jun Hu; Bohui Xu; Xiaoliang Chen; Qi Xue (Journal of Environmental Chemical Engineering, 2023)

Improving the yield and tetracycline adsorption performance of kitchen waste biochar through subcritical dimethyl ether pretreatment - Jipeng Sun; Wei Zhu; Jun Cao; Jun Zhong; Biao Mu; Xin Wang; Naixi Lin (Journal of Environmental Chemical Engineering, 2023)

Antimony immobilization mechanism on schwertmannite: Insights from the microstructure of schwertmannite - Jun Shan; Mengchang He; Peng Liu; Wenting Wang; Chunye Lin; Wei Ouyang; Xitao Liu; Jianwei Zhou; Haijiao Xie (Geochimica et Cosmochimica Acta, 2023)

Mini-Review: The Diagnostic Methods of Tinea Capitis - Lin-wei Wei; Jian-jun Qiao (Mycopathologia, 2023)

Drynaria Naringin alleviated mechanical stress deficiency-caused bone loss deterioration via Rspo1/Lgr4-mediated Wnt/β-catenin signalling pathway - Gui-Xun Shi; Wei-Dong Sun; Zeng-Huan Chen; Chuan-Jun Yang; Wang-Lin Luo; Dan-Feng Wang; Ze-Zhu Zhou (In Vitro Cellular & Developmental Biology - Animal, 2023)

Research on stability and control strategies for a spring-loaded valve with bypass outlet - Jie Jian; Zhi-Jun Shuai; Jia-Xuan He; Chang-Lin Meng; Tao Yu; Xi Wang; Wan-You Li; Shi-Wei Ni; Chen-Xing Jiang (Annals of Nuclear Energy, 2023)

Development of microfluidic chip flowmeter-based constant pressure system for analysing the hydrogen adsorption performance of non-evaporable getters - Wenyu Lin; Wei Wei; Jun Wu; Qing Cao; Hailin Bi; Jun Zhang; Zhengwei Mei; Jian Jin; Xudi Wang (Analytica Chimica Acta, 2023)

Effects of Fermented Cottonseed Meal Substitution for Fish Meal on Intestinal Enzymatic Activity, Inflammatory and Physical-Barrier-Related Gene Expression, and Intestinal Microflora of Juvenile Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Xiaolin Huang; Heizhao Lin; Maoyan Luo; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2023)
The present study was conducted to investigate the effects of dietary fermented cottonseed meal (FCSM) substitution for fish meal on intestinal enzymatic activity, inflammatory and physical-barrier-related gene expression, and intestinal microflora of juvenile golden pompano. The 375 golden pompanos were divided into 15 groups of 25 fish each, with three replicates for each experimental group. The fish were fed five experimental diets (0 (FM), 12.5% (CSM12.5), 25% (CSM25), 50% (CSM50), and 100% (CSM100) substitution levels) for 8 weeks. The fish were reared and fed the experimental diets under a natural-day light cycle. Compared with the control group, the activities of AMY (amylase) enzymes in the CSM12.5 group and all other groups were elevated (p

Toxicity of o-phenylphenol on craniofacial cartilage development through ROS-induced oxidative stress in zebrafish embryos - Xiaomei Chen; Jun Guo; Yong Huang; Zekun Li; Wei Yuan; Suwen Zeng; Hanyi Zhu; Yinliang Zhong; Weiying Lin; Huiqiang Lu; Jian Yang (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Analysis of energy, exergy and CO2 emissions in a fiberglass furnace with oxy-fuel combustion - Yuan Yao; Jun-yao He; Qi Chen; Teng Li; Bo Li; Xiao-lin Wei (Fuel, 2023)

A model for describing advective and diffusive gas transport through initially saturated bentonite with consideration of temperature - Lin-Yong Cui; Wei-Min Ye; Qiong Wang; Yong-Gui Chen; Yu-Jun Cui (Engineering Geology, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Anti-inflammatory ent-cleistanthane-type diterpenoids from Phyllanthus rheophyticus - Hong-Ying Yang; Pei-Zhi Huang; Qian Ma; Yue Sun; Wei-Jiao Feng; Yi-Lin He; Jian-Jun Chen; Kun Gao (Phytochemistry, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Corrigendum to “Association of serum per- and polyfluoroalkyl substances and gestational anemia during different trimesters in Zhuang ethnic pregnancy women of Guangxi, China” [Chemosphere. Dec 2022 309:136798] - Qian Liao; Peng Tang; Dongxiang Pan; Yanye Song; Lei Lei; Jun Liang; Bihu Liu; Mengrui Lin; Huishen Huang; Meile Mo; Chengtuo Huang; Ming Wei; et al. (Chemosphere, 2023)

Short-term motion prediction of floating offshore wind turbine based on muti-input LSTM neural network - Wei Shi; Lehan Hu; Zaibin Lin; Lixian Zhang; Jun Wu; Wei Chai (Ocean Engineering, 2023)

Obstacle avoidance based on double closed loop control of autonomous underwater vehicle for submarine cable laying - Wei-ran Wang; Zhe-hao Su; Hui-lin Ge; Xiao-Qiang Dai; Zhi-yu Zhu; Jie Yao; Qing-jun Zeng (Ocean Engineering, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

Life cycle assessment: Sustainability of biodiesel production from black soldier fly larvae feeding on thermally pre-treated sewage sludge under a tropical country setting - Chin Seng Liew; Guo Ren Mong; Jun Wei Lim; Ratchaprapa Raksasat; Hemamalini Rawindran; Wai Hong Leong; M. Devendran Manogaran; Yee Ho Chai; Yeek Chia Ho; Anisa Ur Rahmah; Chuxia Lin; Kuan Shiong Khoo; et al. (Waste Management, 2023)

Co-incidence of BA.1 and BA.2 at the start of Singapore's Omicron wave revealed by Community and University Campus wastewater surveillance - Feng Jun Desmond Chua; Se Yeon Kim; Eric Hill; Jia Wei Cai; Wei Lin Lee; Xiaoqiong Gu; Siti Aisyah Afri Affandi; Wee Chiew Germaine Kwok; Weijie Ng; Mats Leifels; Federica Armas; Franciscus Chandra; et al. (Science of The Total Environment, 2023)

Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. - Kang Ding; Zi-Yao Wu; Nuan Zhang; Jun He; Fan Zhang; Jing-Jing Wu; Hong-Jin Bai; Wei-Ku Zhang; Lin Li; Jie-Kun Xu (Phytochemistry, 2023)

Sex-specific effect of perfluoroalkyl substances exposure on liver and thyroid function biomarkers: A mixture approach - Ze Yang; Ruifang Liu; Hongbo Liu; Jiemin Wei; Xiaohui Lin; Mingyue Zhang; Yu Chen; Jingyun Zhang; Meiqing Sun; Zhe Feng; Jian Liu; Xiangyang Liu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Epitomizing biohydrogen production from microbes: Critical challenges vs opportunities - Jia Min Woon; Kuan Shiong Khoo; Asla A. AL-Zahrani; Meznah M. Alanazi; Jun Wei Lim; Chin Kui Cheng; Nurul Tasnim Sahrin; Fatima Musa Ardo; Sun Yi-Ming; Kuen-Song Lin; John Chi-Wei Lan; Md Sohrab Hossain; et al. (Environmental Research, 2023)

Durable dual-methylpiperidinium crosslinked poly(binaphthyl-co-terphenyl piperidinium) anion exchange membranes with high ion transport and electrochemical performance - Wei Ting Gao; Xue Lang Gao; Yvonne Shuen Lann Choo; Jia Jun Wang; Zhi Hong Cai; Qiu Gen Zhang; Ai Mei Zhu; Qing Lin Liu (Chemical Engineering Journal, 2023)

Combining orthogonal plant and non-plant fatty acid biosynthesis pathways for efficient production of microbial oil enriched in nervonic acid in Yarrowia lipolytica - Kaifeng Wang; Lu Lin; Ping Wei; Rodrigo Ledesma-Amaro; Xiao-Jun Ji (Bioresource Technology, 2023)

CircFhit Modulates GABAergic Synaptic Transmission via Regulating the Parental Gene Fhit Expression in the Spinal Dorsal Horn in a Rat Model of Neuropathic Pain - Ting Xu; Zhen-Yu Li; Meng Liu; Su-Bo Zhang; Huan-Huan Ding; Jia-Yan Wu; Su-Yan Lin; Jun Liu; Jia-You Wei; Xue-Qin Zhang; Wen-Jun Xin (Neuroscience Bulletin, 2023)

The validation and clinical significance of LPCAT1 down-regulation in acute myeloid leukemia - Qin Chen; Zijun Xu; Jiang Lin; Zhaoqun Deng; Jun Qian; Wei Qian (Molecular Biology Reports, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

Response of soil microbial activities and ammonia oxidation potential to environmental factors in a typical antimony mining area - Aihua Wang; Shujun Liu; Jun Xie; Wei Ouyang; Mengchang He; Chunye Lin; Xitao Liu (Journal of Environmental Sciences, 2023)

Associations of per- and polyfluoroalkyl substances and alternatives with reproductive hormones in women of childbearing age - Caiyun Lin; Min Nian; Meihua Xie; Liangying Zeng; Wei Qiu; Jun Zhang; Hua Yang (International Journal of Hygiene and Environmental Health, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Synergistic analysis of performance, functional genes, and microbial community assembly in SNDPR process under Zn(II) stress - Tong Wu; Jie Ding; Le Zhong; Yi-Lin Zhao; Han-Jun Sun; Ji-Wei Pang; Lei Zhao; Shun-Wen Bai; Nan-Qi Ren; Shan-Shan Yang (Environmental Research, 2023)

Prolonged Mesozoic intracontinental gold mineralization in the South China Block controlled by lithosphere architecture and evolving Paleo-Pacific Plate subduction - Yushan Zeng; Qingfei Wang; David I. Groves; M. Santosh; Yanning Wang; Tingyi Wang; Lin Yang; Wei Chen; Jun Deng (Earth-Science Reviews, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Field experiments on quantifying the contributions of Coreopsis canopies and roots to controlling runoff and erosion on steep loess slopes - Yu-wei Gong; Hai-jun Yu; Pei Tian; Wen-zhao Guo; Lin Chen; Ding-tao Shen (Journal of Mountain Science, 2023)

Characteristics and driving factors of abandoned cultivated land in the hilly regions of southern China: A case study in Longnan, Jiangxi Province - Ze-bin Chen; Yong-lin Chen; Chao-jun Li; Jian-ping Lin; Pei-ru Chen; Wei-wei Sun; Zhi-wei Wan (Journal of Mountain Science, 2023)

Design of the yielding support used highly deformable elements for a tunnel excavated in squeezing rock - Hong-ming Tian; Yun Tian; Wei-zhong Chen; Xian-jun Tan; Xiao-yun Shu; Xia-lin Liu (Journal of Mountain Science, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Arbuscular mycorrhizal fungi increase the interspecific competition between two forage plant species and stabilize the soil microbial network during a drought event: Evidence from the field - Xionghui Liao; Jie Zhao; Lin Xu; Li Tang; Jiangnan Li; Wei Zhang; Jun Xiao; Dan Xiao; Peilei Hu; Yunpeng Nie; Dongsheng Zou; Kelin Wang (Applied Soil Ecology, 2023)

Dietary chitosan alleviates intestinal and liver injury of hybrid sturgeon (Acipenser baerii♀ × A. schrenckii♂) induced by Aeromonas hydrophila infection - Ruiran Li; Xiaoni Wang; Denghang Yu; Qianrong Liang; Fuguo Liu; Lin Zhang; Bing Hu; Jin Wei; Lihe Liu; Jun Liu; Hongsen Xu (Animal Feed Science and Technology, 2023)

Aestuariibaculum lutulentum sp. nov., a marine bacterium isolated from coastal sediment in Beihai - Jia-Wei Gao; Dong-Yan He; Wen-Wu Zhang; Yu-Ruo Wang; Yue Su; Jun-Jie Ying; Zhi-Cheng Wu; Wu Qu; Lin Xu; Cong Sun (Archives of Microbiology, 2023)

Toxicological characteristics of drinking water in two large-scale municipal water supply systems of a metropolitan city in Central China - Huai-Ji Wang; Chen-Wei Peng; Xue Han; Yan Wang; Jie Zhang; Jun-Ling Liu; Meng-Xuan Zhou; Fei Tang; Ai-Lin Liu (Environmental Science and Pollution Research, 2023)

Triassic granitoids in the East Kunlun Orogenic Belt, Northwestern China: magmatic source and implications for geodynamic evolution - Zhi-He Xu; Wei Xin; Xiao-Dong Zhou; Qing-Lin Xu; Fu-Wen Li; Zhao-Jun Song (International Geology Review, 2023)

Chronic environmental inorganic arsenic exposure causes social behavioral changes in juvenile zebrafish (Danio rerio) - Yi-Hong Wang; Ya-Qian Wang; Xiao-Gang Yu; Yin Lin; Jun-Xia Liu; Wei-Ye Wang; Chong-Huai Yan (Science of The Total Environment, 2023)

Optimizing the parameters of microbial fuel cells using response surface methodology to increase Cr(VI) removal efficiency and power production - Chi-Wen Lin; Yi-Pei Chung; Shu-Hui Liu; Wei Tong Chen; Ting-Jun Zhu (Process Safety and Environmental Protection, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

Designing direct redox reaction chemically coupling NO and SO2 removal - Dongyue Zhao; Qiuqiao Jiang; Bo Peng; Jun Liu; Ruoyu Wang; Menglong Feng; Shangcong Sun; Hao Sha; Kai Zhu; Haitao Song; Wei Lin; Zhijian Da (Fuel, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Periodate activation with stable MgMn2O4 spinel for bisphenol A removal: Radical and non-radical pathways - Jiaxin Yu; Wei Qiu; Xinchen Lin; Yishi Wang; Xiaohui Lu; Yongbo Yu; Haiteng Gu; Song Heng; Haochen Zhang; Jun Ma (Chemical Engineering Journal, 2023)

Highly selective monoclonal antibody-based fluorescence immunochromatographic assay for the detection of fenpropathrin in vegetable and fruit samples - Zi-Hong Xu; Jun-Kai Wang; Qiu-Xiong Ye; Lin-Feng Jiang; Hao Deng; Jun-Fa Liang; Run-Xi Chen; Wei Huang; Hong-Tao Lei; Zhen-Lin Xu; Lin Luo (Analytica Chimica Acta, 2023)

Cobalt exposure and dyslipidemia in elderly population: the mediating role of systemic inflammation and lipid peroxidation - Jia-Hui Huang; Li Tao; Yi Wu; Wei He; Jun-Xian Wang; Xi Chen; Lin Fu (Environmental Science and Pollution Research, 2023)

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

The study on the main mode of the death of red blood cells in grass carp (Ctenopharyngodon idella) - Hong Chen; Minshan Yao; Ying Tang; Lixiang Wei; Junyan Lin; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Study on the regulatory mechanism of erythropoietin in erythropoiesis in grass carp (Ctenopharyngodon idella) - Junyan Lin; Lixiang Wei; Minshan Yao; Hong Chen; Ying Tang; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Water quality criteria derivation and tiered ecological risk evaluation of antifouling biocides in marine environment - Hai-Wei Luo; Min Lin; Xin-Xin Bai; Bin Xu; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Pre-exposure of peracetic acid enhances its subsequent combination with ultraviolet for the inactivation of fungal spores: Efficiency, mechanisms, and implications - Wei Lin; Jie Zuo; Kai Li; Ruizhu Hu; Xiangqian Xu; Tinglin Huang; Gang Wen; Jun Ma (Water Research, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways - Jhe-Wei Lin; Shih-Chang Fu; Jui-Ming Liu; Shing-Hwa Liu; Kuan-I Lee; Kai-Min Fang; Ren-Jun Hsu; Chun-Fa Huang; Kun-Min Liu; Kai-Chih Chang; Chin-Chuan Su; Ya-Wen Chen (Toxicology in Vitro, 2023)

Reducing manufacturing carbon emissions: Optimal low carbon production strategies respect to product structures and batches - Jun Zheng; Junjie Shi; Feng Lin; Xinyu Hu; Qi Pan; Tiening Qi; Yicheng Ren; Aizhi Guan; Zhiyi Zhang; Wei Ling (Science of The Total Environment, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Activation of persulfate by vanadium oxide modified carbon nanotube for 17β-estradiol degradation in soil: Mechanism, application and ecotoxicity assessment - Zhou Zhou; Xitao Liu; Jun Ma; Jun Huang; Chunye Lin; Mengchang He; Wei Ouyang (Science of The Total Environment, 2023)

Enhanced sludge dewaterability by ferrate/ferric chloride: The key role of Fe(IV) on the changes of EPS properties - Wei Lin; Junmin Guo; Jie Zeng; Renglu Chen; Huu Hao Ngo; Jun Nan; Guibai Li; Jun Ma; An Ding (Science of The Total Environment, 2023)

Bedrock outcrops weakly promote rather than inhibit soil carbon sequestration after vegetation restoration - Lin Xu; Jiguang Zhang; Peilei Hu; Wei Zhang; Lumei Xiao; Yingying Ye; Dan Xiao; Jie Zhao; Jun Xiao; Kelin Wang (Science of The Total Environment, 2023)

Bibliometric overview of research progress, challenges, and prospects of rural domestic sewage: Treatment techniques, resource recovery, and ecological risk - Le Zhong; Jie Ding; Tong Wu; Yi-lin Zhao; Ji Wei Pang; Ji-Ping Jiang; Jun-Qiu Jiang; Yan Li; Nan-Qi Ren; Shan-Shan Yang (Journal of Water Process Engineering, 2023)

Analysis of degradation kinetic modeling and mechanism of chlorinated-halonitromethanes under UV/monochloramine treatment - Bohui Xu; Lin Deng; Shizheng Zhang; Wei Luo; Jun Hu; Chaoqun Tan; Rajendra Prasad Singh (Environmental Pollution, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Sulfur isotope, fluid inclusions, and quartz solubility model decipher multistage hydrothermal fluids evolution and ore precipitation mechanism at the Nantai porphyry Mo deposit, Qinling, Central China - Zhong-Yu Zhang; Yin-Hong Wang; Jia-Jun Liu; Shan-Yuan Lin; Fang-Fang Zhang; Wei Zhang; Zhen-Yu Bo; Hui Zhang; Hong-Yu Li (Chemical Geology, 2023)

A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304 - Xin Qi; Wei-Hao Chen; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Yong-Hong Liu; Jun-Feng Wang; Yong Li (Natural Product Research, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Application of a new basalt fiber-reinforced polymer anchorage structure in the tunnel—slope system under rainfall action - Lin Tang; Hong-gang Wu; Hong Wei; Kang Feng; Guo-jun Reng (Journal of Mountain Science, 2023)

Seasonal spermatogenesis, epididymal storage, and creatine kinase expression in Pelodiscus sinensis - Yu-Fei Yang; Jia-Hao Wu; Run-Lan Lin; Shang-Jun Yin; Guo-Ying Qian; Wei Wang; Yong-Doo Park (Animal Reproduction Science, 2023)

The Impacts of Dietary Curcumin on Innate Immune Responses and Antioxidant Status in Greater Amberjack (Seriola dumerili) under Ammonia Stress - Chuanpeng Zhou; Zhong Huang; Shengjie Zhou; Jing Hu; Rui Yang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma (Journal of Marine Science and Engineering, 2023)
In this study, we investigated the effect of dietary curcumin on non-specific immune responses and antioxidative ability in Seriola dumerili under ammonia stress and post-recovery. Three diets were prepared to contain 0, 75, and 150 mg/kg of curcumin. A total of 225 greater amberjack (initial weight: 100.90 ± 0.03 g) were distributed into nine cylindrical tanks, constituting an experimental design with three treatments and three replicates. After 56 days of feeding, plasma, intestinal, and hepatic enzyme activities were evaluated. Then, an acute ammonia challenge experiment was conducted. Ten fish per tank were subjected to acute ammonia stress (total ammonia-N: 1000 mg/L) for eight minutes followed by six minutes of recovery. The results indicated that dietary curcumin significantly promoted intestinal and hepatic alkaline phosphatase (ALP) and acid phosphatase (ACP) levels as well as hepatic antioxidative enzymes such as superoxide dismutase (SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) of greater amberjack. In addition, curcumin addition improved the activities of antioxidant enzymes, such as SOD, T-AOC, GSH, GSH-Px, and catalase (CAT), and reduced malondialdehyde (MDA) content in liver, spleen, head kidney, and brain tissues after post-recovery. The indexes related to immunity and antioxidant enzymes in the liver, gill, and spleen rose again to some extent, but they showed the worst recovery ability in the head kidney and brain tissue samples. These results indicate that dietary curcumin supplementation could increase non-specific immune responses, antioxidant ability, and enhance resistance to high ammonia stress in juvenile S. dumerili.

Association between exposure to perfluoroalkyl substances and uric acid in Chinese adults - Ze Yang; Kun Men; Jiaxin Guo; Ruifang Liu; Hongbo Liu; Jiemin Wei; Jingyun Zhang; Liangpo Liu; Xiaohui Lin; Mingyue Zhang; Yong Liu; Yu Chen; et al. (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Effect of hydrothermal pretreatment and compound microbial agents on compost maturity and gaseous emissions during aerobic composting of kitchen waste - Ting Xie; Zhaohan Zhang; Dawei Zhang; Chunzhong Wei; Yong Lin; Rongwei Feng; Jun Nan; Yujie Feng (Science of The Total Environment, 2023)

Rational design of ordered porous nanoparticles for selective extraction of nitrobenzene compounds - Sheng Peng; Minhui Shen; Xiang Li; Yuan-Jun Tong; Jing Guo; Wei Lin; Yu-Xin Ye; Jianqiao Xu; Ningbo Zhou; Fang Zhu; Gangfeng Ouyang (Journal of Hazardous Materials, 2023)

Correction to: Exposure assessment of aflatoxins and zearalenone in edible vegetable oils in Shandong, China: health risks posed by mycotoxin immunotoxicity and reproductive toxicity in children - Fenghua Li; Xianqi Zhao; Yanni Jiao; Xinglan Duan; Lianlong Yu; Fengjia Zheng; Xiaolin Wang; Lin Wang; Jia‑Sheng Wang; Xiulan Zhao; Tianliang Zhang; Wei Li; et al. (Environmental Science and Pollution Research, 2023)

Exposure assessment of aflatoxins and zearalenone in edible vegetable oils in Shandong, China: health risks posed by mycotoxin immunotoxicity and reproductive toxicity in children - Fenghua Li; Xianqi Zhao; Yanni Jiao; Xinglan Duan; Lianlong Yu; Fengjia Zheng; Xiaolin Wang; Lin Wang; Jia-Sheng Wang; Xiulan Zhao; Tianliang Zhang; Wei Li; et al. (Environmental Science and Pollution Research, 2023)

A new formula of recovery factor for non-equilibrium transport of graded suspended sediment in the Middle Yangtze River - Lin-lin Li; Jun-qiang Xia; Mei-rong Zhou; Shan-shan Deng; Zhi-wei Li (Journal of Mountain Science, 2023)

Control measure implications of COVID-19 infection in healthcare facilities reconsidered from human physiological and engineering aspects - Ying-Fei Yang; Yi-Jun Lin; Shu-Han You; Tien-Hsuan Lu; Chi-Yun Chen; Wei-Min Wang; Chung-Min Liao (Environmental Science and Pollution Research, 2022)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

Long‐term series variation in fishery biology of Dosidicus gigas off Peru: Response to climate variability from 2008 to 2020 - Ya Ting Dan; Bi Lin Liu; Xin Jun Chen; Wei Guo Qian (Fisheries Oceanography, 2022)
As a cephalopod with a short life cycle, the Dosidicus gigas (jumbo flying squid) is extremely sensitive to climate variability and marine environment changes in terms of individual growth and resource changes. Based on 7514 D. gigas samples collected off Peru from 2008 to 2020, the fishery biological characteristics such as size, sexual maturity, and size‐at‐maturity were analyzed to explore the impacts of climate variability on individual growth. The results showed that there were significant differences in the relationship between mantle length and body weight and in the composition of sexual maturity between male and female individuals in different years ( P D. gigas and slowed down their sexual maturity, producing D. gigas groups in medium and large sizes; El Niño events inhibited the individual growth of D. gigas and accelerated their sexual maturity, producing D. gigas groups in a smaller size. From 2008 to 2020, the mantle length of the small‐size group decreased by 46 mm, while that of the medium‐size group increased by 28 mm. Size‐at‐maturity of female D. gigas decreased by 201.2 mm and that of male D. gigas decreased by 143 mm. The study concluded that the changes in the marine environment caused by climate variability from 2008 to 2020 have had a significant impact on the population structure, growth, and development of the D. gigas off Peru.

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Geomechanics model test and numerical simulation of 2G-NPR bolt support effect in an active fault tunnel - Shu-lin Ren; Man-chao He; Wei-jun Lin; Teng-wu Zhang; Zhi-gang Tao (Journal of Mountain Science, 2022)

Cluster analysis of the domain of microseismic event attributes for floor water inrush warning in the working face - Guo-Jun Shang; Xiao-Fei Liu; Li Li; Li-Song Zhao; Jin-Song Shen; Wei-Lin Huang (Applied Geophysics, 2022)

Hydrodynamic effects of large-scale suspended mussel farms: Field observations and numerical simulations - Wei Zhong; Jun Lin; Qingping Zou; Ying Wen; Wei Yang; Guanlin Yang (Frontiers in Marine Science, 2022)
The hydrodynamic effects of the largest suspended mussel farms in the East China Sea near Gouqi Island, was investigated using a high-resolution 3D ocean model and field observations. To capture the 3D farm effects on hydrodynamics, an additional depth dependent momentum sink term was introduced in the model. The model results compared well with the field observations. The present model and observational results indicate that the presence of farms reduces the flow by more than 79%, 55%, and 34% in the upper, middle, and bottom layers at the farm center, respectively. According to the harmonic analysis of predicted current, mussel farms reduce the magnitude of the semidiurnal tidal current and also alter the magnitude and direction of the diurnal tidal current. The blockage by the farm weakens the Eulerian residual tidal current within the farm in the NE-SW direction, while strengthens that at the edge of the farm in the SE-NW direction. Cross sections, Sec1 and Sec2 are perpendicular to these two major residual currents and intercept with the center of the farm from SE to NW and from NE to SW respectively. The farm effect on the total water flux over a month through the Sec2 displays a semi-lunar periodic oscillation and is one order of magnitude smaller than that at Sec1. An asymmetry tidal current was observed in the farm north of Gouqi Island. The field observation of vertical profiles of current suggests that the thickness of surface canopy boundary layer can reach 5 m upstream from the farm during flood tide, increases gradually downstream up to 10 m under the cumulative influences of the farm. And a wake zone was observed downstream from the farm during flood tide. Better understanding of farm-induced hydrodynamic effects provides insight into how to optimize farm layouts based on local hydrodynamics, to maximize farm productivity and minimize environmental impacts.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Assessing the effect of probiotics on tilapia lake virus‐infected tilapia: Transmission and immune response - Ying‐Fei Yang; Jidapa Yamkasem; Win Surachetpong; Yi‐Jun Lin; Shu‐Han You; Tien‐Hsuan Lu; Chi‐Yun Chen; Wei‐Min Wang; Chung‐Min Liao (Journal of Fish Diseases, 2022)
Probiotics have been used to alleviate disease transmission in aquaculture. However, there are limited studies on probiotic use in modulating tilapia lake virus (TiLV). We assessed commercially available probiotic supplements used in TiLV‐infected tilapia and performed mortality and cohabitation assays. We developed a mechanistic approach to predict dose–response interactions of probiotic effects on mortality and immune gene response. We used a susceptible–infected–mortality disease model to assess key epidemiological parameters such as transmission rate and basic reproduction number ( R 0 ) based on our viral load dynamic data. We found that the most marked benefits of probiotics are significantly associated with immune system enhancements (~30%) and reductions in disease transmission (~80%) and R 0 (~70%) in tilapia populations, resulting in a higher tolerance of farming densities (~400 fold) in aquaculture. These findings provide early insights as to how probiotic use‐related factors may influence TiLV transmission and the immune responses in TiLV‐infected tilapia. Our study facilitates understanding the mode of action of probiotics in disease containment and predicting better probiotic dosages in diet and supplements to achieve the optimal culturing conditions. Overall, our analysis assures that further study of rationally designed and targeted probiotics, or mechanistic modelling is warranted on the basis of promising early data of this approach.

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

The optimal combination of Nile red identification, colony polymerase chain reaction, and gas chromatography detection methods in screening for polyhydroxyalkanoicate-producing bacteria - Hung-Che Chou; Chia-Hsin Chen; Hsiao-Kai Chu; Chun-Mei Huang; Hui-Jun Wang; Wei-Lin Tu; Gia-Luen Guo (Archives of Microbiology, 2022)

Natural component plumbagin as a potential antibacterial agent against Streptococcus agalactiae infection - Ai‐Guo Huang; Lin‐Jun Su; Wei‐Hao He; Fa‐Li Zhang; Chao‐Shuai Wei; Ying‐Hui Wang (Journal of Fish Diseases, 2022)
Streptococcus agalactiae , also known as Group B Streptococcus (GBS), can infect humans, terrestrial animals and fish. The emergence of bacterial resistance of S. agalactiae to antibiotics leads to an urgent need of exploration of new antimicrobial agents. In the study, the antibacterial activity of natural component plumbagin (PLB) against S. agalactiae was investigated in vitro and in vivo. The results showed that the minimal inhibitory concentration (MIC) of PLB against S. agalactiae was 8 mg/L. The growth curve assay revealed that PLB could inhibit the growth of S. agalactiae . In addition, the time‐killing curve showed that S. agalactiae was killed almost completely by 2‐fold MIC of PLB within 12 h. Transmission electron microscopy results showed obvious severe morphological destruction and abnormal cells of S. agalactiae after treated with PLB. The pathogenicity of S. agalactiae to zebrafish was significantly decreased after preincubation with PLB for 2 h in vitro, further indicating the bactericidal activity of PLB. Interestingly, PLB could kill S. agalactiae without inducing resistance development. Furthermore, pretreatment and post‐treatment assays suggested that PLB also exhibited the antibacterial activity against S. agalactiae infection in vivo by effectively reducing the bacterial load and improving the survival rate of S. agalactiae ‐infected zebrafish. In summary, PLB had potent antibacterial activity against S. agalactiae in vitro and in vivo, and it could be an excellent antimicrobial candidate to prevent and control S. agalactiae infection.

Effects of Involuntary and Voluntary Exercise in Combination with Acousto-Optic Stimulation on Adult Neurogenesis in an Alzheimer's Mouse Model - Wan-yi Li; Jun-yan Gao; Su-Yang Lin; Shao-tao Pan; Biao Xiao; Yu-tao Ma; Kai Xie; Wei Shen; Zhi-tao Liu; Guang-yu Li; Jie-jie Guo; Qin-wen Wang; et al. (Molecular Neurobiology, 2022)

Links between continental subduction and generation of Cenozoic potassic–ultrapotassic rocks revealed by olivine oxygen isotopes: A case study from NW Tibet - Gong-Jian Tang; Derek A. Wyman; Qiang Wang; Lin Ma; Wei Dan; Ya-Nan Yang; Xi-Jun Liu; Hong-Yi Chen (Contributions to Mineralogy and Petrology, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

Two new 7,20-epoxy- ent -kaurane diterpenoids from the aerial parts of Isodon serra - Juan-Juan Hu; Bai-Lin Li; Jin-Dan Xie; Hui-Jun Liang; Qian-Ran Li; Jie Yuan; Jie-Wei Wu (Natural Product Research, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

Water Circulation Driven by Cold Fronts in the Wax Lake Delta (Louisiana, USA) - Qian Zhang; Chunyan Li; Wei Huang; Jun Lin; Matthew Hiatt; Victor H. Rivera-Monroy (Journal of Marine Science and Engineering, 2022)
Atmospheric cold fronts can periodically generate storm surges and affect sediment transport in the Northern Gulf of Mexico (NGOM). In this paper, we evaluate water circulation spatiotemporal patterns induced by six atmospheric cold front events in the Wax Lake Delta (WLD) in coastal Louisiana using the 3-D hydrodynamic model ECOM-si. Model simulations show that channelized and inter-distributary water flow is significantly impacted by cold fronts. Water volume transport throughout the deltaic channel network is not just constrained to the main channels but also occurs laterally across channels accounting for about a quarter of the total flow. Results show that a significant landward flow occurs across the delta prior to the frontal passage, resulting in a positive storm surge on the coast. The along-channel current velocity dominates while cross-channel water transport occurs at the southwest lobe during the post-frontal stage. Depending on local weather conditions, the cold-front-induced flushing event lasts for 1.7 to 7 days and can flush 32–76% of the total water mass out of the system, a greater range of variability than previous reports. The magnitude of water flushed out of the system is not necessarily dependent on the duration of the frontal events. An energy partitioning analysis shows that the relative importance of subtidal energy (10–45% of the total) and tidal energy (20–70%) varies substantially from station to station and is linked to the weather impact. It is important to note that within the WLD region, the weather-induced subtidal energy (46–66% of the total) is much greater than the diurnal tidal energy (13–25% of the total). The wind associated with cold fronts in winter is the main factor controlling water circulation in the WLD and is a major driver in the spatial configuration of the channel network and delta progradation rates.

Reasonable application range of flocculation–solidification combined method in treatment of hydraulically dredged mud slurry - Rong-Jun Zhang; Zhi-Hao Xu; Jun-Jie Zheng; Lin-Wei Tu; Zhan-fang Huang (Marine Georesources & Geotechnology, 2022)

Anti-proliferative cassane-type diterpenoids from the seeds of Caesalpinia minax - Yunshao Xu; Wei Shi; Lu Feng; Jun Cao; Zheling Feng; Qingwen Zhang; Jinjian Lu; Yang Ye; Ligen Lin (Natural Product Research, 2022)

Evaluation of reference genes for normalization of mRNA and microRNA expression by RT-qPCR under different experimental conditions in Medicago ruthenica (L.) Ledeb. - Mao-Wei Guo; Lin Zhu; Hong-Yan Li; Zi-Nian Wu; Zhi-Yong Li; Jun Li (Genetic Resources and Crop Evolution, 2022)

Pilot study on the treatment of low carbon and nitrogen ratio municipal sewage by A1/O2/A3/A4/O5 sludge-membrane coupling process with multi-point inflow - De-Wei Zhang; Jun-Tian Zheng; Jun Zheng; Meng-Ke Zhao; Meng-Lin Wang; Shi-Hua Zhang (Environmental Science and Pollution Research, 2022)

Sabulicella rubraurantiaca gen. nov., sp. nov., a new member of the family Acetobacteraceae, isolated from desert soil - Zhi-Liang Lin; Shuai Li; Qi-Chuang Wei; Wen-Hui Lian; Chun-Yan Lu; Lu Xu; Li-Nan Huang; Lei Dong; Wen-Jun Li (Archives of Microbiology, 2022)

Responses of soil pH to no‐till and the factors affecting it: A global meta‐analysis - Xin Zhao; Cong He; Wen‐Sheng Liu; Wen‐Xuan Liu; Qiu‐Yue Liu; Wei Bai; Li‐Jun Li; Rattan Lal; Hai‐Lin Zhang (Global Change Biology, 2022)
No‐till (NT) is a sustainable option because of its benefits in controlling erosion, saving labor, and mitigating climate change. However, a comprehensive assessment of soil pH response to NT is still lacking. Thus, a global meta‐analysis was conducted to determine the effects of NT on soil pH and to identify the influential factors and possible consequences based on the analysis of 114 publications. When comparing tillage practices, the results indicated an overall significant decrease by 1.33 ± 0.28% in soil pH under NT than that under conventional tillage ( p −1 (−1.83%), or crop residue retention (−1.52%). Changes in organic matter decomposition under undisturbed soil and with crop residue retention might lead to a higher concentration of H + and lower of basic cations (i.e., calcium, magnesium, and potassium), which decrease the soil pH, and consequently, impact nutrient dynamics (i.e., soil phosphorus) in the surface layer under NT. Furthermore, soil acidification may be aggravated by NT within site‐specific conditions and improper fertilizer and crop residue management and consequently leading to adverse effects on soil nutrient availability. Thus, there is a need to identify strategies to ameliorate soil acidification under NT to minimize the adverse consequences.

Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

Associations of bisphenol exposure with the risk of gestational diabetes mellitus: a nested case–control study in Guangxi, China - Peng Tang; Jun Liang; Qian Liao; Huishen Huang; Xiaojing Guo; Mengrui Lin; Bihu Liu; Bincai Wei; Xiaoyun Zeng; Shun Liu; Dongping Huang; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2021)

Linking circular intronic RNA degradation and function in transcription by RNase H1 - Xiang Li; Jia-Lin Zhang; Yun-Ni Lei; Xiao-Qi Liu; Wei Xue; Yang Zhang; Fan Nan; Xiang Gao; Jun Zhang; Jia Wei; Li Yang; Ling-Ling Chen (Science China Life Sciences, 2021)

Depression Augments Plasma APOA4 without Changes of Plasma Lipids and Glucose in Female Adolescents Carrying G Allele of APOA4 rs5104 - Qi Wei Guo; Yan Jun Si; Yi Lin Shen; Xu Chen; Mei Yang; Ding Zhi Fang; Jia Lin (Journal of Molecular Neuroscience, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Fast estimation method of volumes of landslide deposit by the 3D reconstruction of smartphone images - Lin Fu; Jun Zhu; Wei-lian Li; Ji-gang You; Zhang-yu Hua (Landslides, 2021)

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

The major photoprotective role of anthocyanins in leaves of Arabidopsis thaliana under long-term high light treatment: antioxidant or light attenuator? - Xiao-Ting Zheng; Zheng-Chao Yu; Jun-Wei Tang; Min-Ling Cai; Yi-Lin Chen; Cheng-Wei Yang; Wah Soon Chow; Chang-Lian Peng (Photosynthesis Research, 2021)

Relationship between heavy metal consolidation and H2S removal by biochar from microwave pyrolysis of municipal sludge: effect and mechanism - Qingyuan Lin; Jun Zhang; Linlin Yin; Hao Liu; Wei Zuo; Yu Tian (Environmental Science and Pollution Research, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Upregulation of long noncoding RNA XIST has anticancer effects on ovarian cancer through sponging miR-106a - Ting Guo; Donglan Yuan; Wei Zhang; Dandan Zhu; Aifang Xiao; Guangyao Mao; Wenjuan Jiang; Mei Lin; Jun Wang (Human Cell, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Injection route affects intra-articular hyaluronic acid distribution and clinical outcome in viscosupplementation treatment for knee osteoarthritis: a combined cadaver study and randomized clinical trial - Jun Xiao; Yong Hu; Lin Huang; Zhi-Fa Huang; Wei-Zhou Jiang; Yu-Qiang Luo; Meng-Yan Jia; Di Chen; Zhan-Jun Shi (Drug Delivery and Translational Research, 2021)

Correction to: Glaciimonas soli sp. nov., a soil bacterium isolated from the forest of a high elevation mountain - Wei-Sheng Huang; Li-Ting Wang; Jun-Ning Sun; Jwo-Sheng Chen; Ssu-Po Huang; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

The involvement of α‐proteobacteria Phenylobacterium in maintaining the dominance of toxic Microcystis blooms in Lake Taihu, China - Jun Zuo; Lili Hu; Wei Shen; Jiaying Zeng; Lin Li; Lirong Song; Nanqin Gan (Environmental Microbiology, 2021)
Summary Lake Taihu in China has suffered serious harmful cyanobacterial blooms for decades. The algal blooms threaten the ecological sustainability, drinking water safety, and human health. Although the roles of abiotic factors (such as water temperature and nutrient loading) in promoting Microcystis blooms have been well studied, the importance of biotic factors (e.g. bacterial community) in promoting and meditating Microcystis blooms remains unclear. In this study, we investigated the ecological dynamics of bacterial community, the ratio of toxic Microcystis , as well as microcystin in Lake Taihu. High‐throughput 16S rRNA sequencing and principal component analysis (PCA) revealed that the bacteria community compositions (BCCs) clustered into three groups, the partitioning of which corresponded to that of groups according to the toxic profiles (the ratio of toxic Microcystis to total Microcystis , and the microcystin concentrations) of the samples. Further Spearman's correlation network showed that the α‐proteobacteria Phenylobacterium strongly positively correlated with the toxic profiles. Subsequent laboratory chemostats experiments demonstrated that three Phenylobacterium strains promoted the dominance of the toxic Microcystis aeruginosa PCC7806 when co‐culturing with the non‐toxic PCC7806 mcyB − mutant. Taken together, our data suggested that the α‐proteobacteria Phenylobacterium may play a vital role in the maintenance of toxic Microcystis dominance in Lake Taihu.

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Pullout Behavior of Sensor-Enabled Geobelts in Weathered Rock Material–Granulated Rubber Mixtures - Yi-lin Wang; Xin-zhuang Cui; Jin Li; Lei Wang; Jun Li; Jun-wei Su (Geotechnical and Geological Engineering, 2021)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

Erythropoietin-Induced Autophagy Protects Against Spinal Cord Injury and Improves Neurological Function via the Extracellular-Regulated Protein Kinase Signaling Pathway - Lin Zhong; Hui Zhang; Zheng-Fei Ding; Jian Li; Jin-Wei Lv; Zheng-Jun Pan; De-Xiang Xu; Zong-Sheng Yin (Molecular Neurobiology, 2020)

Effect of dietary isoleucine on skin mucus barrier and epithelial physical barrier functions of hybrid bagrid catfish Pelteobagrus vachelli × Leiocassis longirostris - Long Yin; Ye Zhao; Xiao-Qiu Zhou; Chao Yang; Lin Feng; Yang Liu; Wei-Dan Jiang; Pei Wu; Jian Zhou; Juan Zhao; Jun Jiang (Fish Physiology and Biochemistry, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Genome-wide identification of the Sec-dependent secretory protease genes in Erwinia amylovora and analysis of their expression during infection of immature pear fruit - Wang-bin Zhang; Hai-lin Yan; Zong-cai Zhu; Chao Zhang; Pei-xiu Du; Wen-jun Zhao; Wei-min Li (Journal of Zhejiang University-SCIENCE B, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

The dynamic process of dietary soybean β-conglycinin in digestion, absorption, and metabolism among different intestinal segments in grass carp (Ctenopharyngodon idella) - Xu-Dong Duan; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Bei-Ping Tan; Qi-Hui Yang; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Seonamhaeicola sediminis sp. nov., isolated from marine sediment - Xiao-Yu Zhang; Rui Zhang; Yan-Lin Zhong; Dai-Wei Xianyu; Zong-Jun Du (Archives of Microbiology, 2020)

Glaciimonas soli sp. nov., a soil bacterium isolated from the forest of a high elevation mountain - Wei-Sheng Huang; Li-Ting Wang; Jun-Ning Sun; Jwo-Sheng Chen; Ssu-Po Huang; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2020)

Miscanthus cultivation shapes rhizosphere microbial community structure and function as assessed by Illumina MiSeq sequencing combined with PICRUSt and FUNGUIld analyses - Yan Chen; Wei Tian; Yang Shao; Ying-Jun Li; Li-An Lin; Ying-Jun Zhang; Hui Han; Zhao-Jin Chen (Archives of Microbiology, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Comparative transcriptomic analysis of fireflies (Coleoptera: Lampyridae) to explore the molecular adaptations to fresh water - Qi‐Lin Zhang; Hong‐Wei Li; Zhi‐Xiang Dong; Xiao‐Jie Yang; Lian‐Bing Lin; Jun‐Yuan Chen; Ming‐Long Yuan (Molecular Ecology, 2020)
Aquatic insects are well adapted to freshwater environments, but the molecular basis of these adaptations remains largely unknown. Most firefly species (Coleoptera: Lampyridae) are terrestrial, but the larvae of several species are aquatic. Here, larval and adult transcriptomes from Aquatica leii (freshwater) and Lychnuris praetexta (terrestrial) were generated to test whether the genes associated with metabolic efficiency and morphology have undergone adaptive evolution to fresh water. The aquatic fireflies had a significantly lower ratio of nonsynonymous to synonymous substitutions than the terrestrial insects, indicating a genomewide evolutionary constraint in the aquatic fireflies. We identified 341 fast‐evolving genes and 116 positively selected genes in the aquatic fireflies. Of these, 76 genes exhibiting both fast evolution and positive selection were primarily involved in ATP production, energy metabolism and the hypoxia response. We identified 7,271 differentially expressed genes (DEGs) in A . leii (adults versus larvae) and 8,309 DEGs in L . praetexta (adults versus larvae). DEGs specific to the aquatic firefly ( n = 1,445) were screened via interspecific comparisons ( A . leii versus L . praetexta ) and were significantly enriched for genes involved in metabolic efficiency (e.g., ATP production, hypoxia, and immune responses) and certain aspects of morphology (e.g., cuticle chitin, tracheal and compound eye morphology). These results indicate that sequence and expression‐level changes in genes associated with both metabolic efficiency and morphological attributes related to the freshwater lifestyle contributed to freshwater adaptation in fireflies. This study provides new insights into the molecular mechanisms of aquatic adaptation in insects.

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Assessing dietary exposure risk to neonicotinoid residues among preschool children in regions of Taiwan - Min-Pei Ling; Huai-An Hsiao; Szu-Chieh Chen; Wei-Yu Chen; Wei-Chun Chou; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Hsing-Chieh Lin; Chi-Yun Chen; Tien-Hsuan Lu; Chung-Min Liao (Environmental Science and Pollution Research, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Soil particle-size distribution and aggregate stability of new reconstructed purple soil affected by soil erosion in overland flow - Feng-Lin Zuo; Xiao-Yan Li; Xiao-Fan Yang; Yang Wang; Yu-Jun Ma; Yu-Han Huang; Chao-Fu Wei (Journal of Soils and Sediments, 2020)

Quantitatively ranking the influencing factors of ammonia volatilization from paddy soils by grey relational entropy - Wen-Ming Xie; Shi-Jun Li; Wei-Ming Shi; Hai-Lin Zhang; Fang Fang; Guo-Xiang Wang; Li-Min Zhang (Environmental Science and Pollution Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Variation of rill cross-sections with gravel and aggregating soil in the Dry-Hot Valley (SW China) - Nana Wang; Lin Ding; Gangcai Liu; Qingchun Deng; Hui Liu; Jie Wang; Wei Lv; Jun Luo; Ziyin Du; Bin Zhang (Modeling Earth Systems and Environment, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Soybean glycinin decreased growth performance, impaired intestinal health, and amino acid absorption capacity of juvenile grass carp (Ctenopharyngodon idella) - Ya-Lin Zhang; Xu-Dong Duan; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Wu-Neng Tang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2019)

Dietary tryptophan affects growth performance, digestive and absorptive enzyme activities, intestinal antioxidant capacity, and appetite and GH–IGF axis-related gene expression of hybrid catfish (Pelteobagrus vachelli♀ × Leiocassis longirostris♂) - Ye Zhao; Xiao-yun Wu; Shang-xiao Xu; Jia-yuan Xie; Kai-wen Xiang; Lin Feng; Yang Liu; Wei-dan Jiang; Pei Wu; Juan Zhao; Xiao-qiu Zhou; Jun Jiang (Fish Physiology and Biochemistry, 2019)

The impact and mechanism of quaternary ammonium compounds on the transmission of antibiotic resistance genes - Yue Han; Zhen-Chao Zhou; Lin Zhu; Yuan-Yuan Wei; Wan-Qiu Feng; Lan Xu; Yang Liu; Ze-Jun Lin; Xin-Yi Shuai; Zhi-Jian Zhang; Hong Chen (Environmental Science and Pollution Research, 2019)

Seasonal Dynamics of Gastrointestinal Nematode Infections of Goats and Emergence of Ivermectin Resistance in Haemonchus contortus in Hubei Province, China - Wei Yuan; Ke Lu; Hao Li; Jinming Liu; Chuanchuan He; Jintao Feng; Xin Zhang; Yudan Mao; Yang Hong; Yu Zhou; Jun Lu; Yamei Jin; et al. (Acta Parasitologica, 2019)

MOF Capacitates Cyclodextrin to Mega-Load Mode for High-Efficient Delivery of Valsartan - Wei Zhang; Tao Guo; Caifen Wang; Yuanzhi He; Xi Zhang; Guangyu Li; Yizhi Chen; Jun Li; Yangjing Lin; Xu Xu; Li Wu; Suxia Zhang; et al. (Pharmaceutical Research, 2019)

3D-QSAR, molecular docking, and new compound design of pyrimidine derivatives as Src small molecule inhibitors - Jun-wei Wang; Ya-ting Deng; Han Chu; Juan Wang; Yong Hu; Zhi-hua Lin (Medicinal Chemistry Research, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Posttraumatic Stress Disorder Augments Plasma Triglycerides in TT Homozygotes of rs495225 at Growth Hormone Secretagogue Receptor Gene - Mi Su; Yan Jun Si; Qi Wei Guo; Mei Yang; Xu Chen; Jia Lin; Ding Zhi Fang (Biochemical Genetics, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Permian integrative stratigraphy and timescale of China - Shuzhong Shen; Hua Zhang; Yichun Zhang; Dongxun Yuan; Bo Chen; Weihong He; Lin Mu; Wei Lin; Wenqian Wang; Jun Chen; Qiong Wu; Changqun Cao; et al. (Science China Earth Sciences, 2019)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

The influences of industrial gross domestic product, urbanization rate, environmental investment, and coal consumption on industrial air pollutant emission in China - Wei-yu Zhou; Wen-lin Yang; Wen-xin Wan; Jing Zhang; Wei Zhou; Hao-shen Yang; Hua Yang; Hong Xiao; Shi-huai Deng; Fei Shen; Ying-jun Wang (Environmental and Ecological Statistics, 2018)

Response to “Letter to the editor re: Cheng YH, Chou WC, Yang YF, et al. Environ Sci Pollut Res (2018). https://doi.org/10.107/s11356-017-0875-4” - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

Preference and performance of the two-spotted spider mite Tetranychus urticae (Acari: Tetranychidae) on strawberry cultivars - Ya-Jun Gong; Jin-Cui Chen; Liang Zhu; Li-Jun Cao; Gui-Hua Jin; Ary A. Hoffmann; Chuan-Fei Zhong; Peng Wang; George Lin; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

Neuroinflammation and Neuroimmunomodulation in Alzheimer’s Disease - Yin Hong; Jun Xu; Yue Hu; Lin Li; Zhen Dong; Ting-ke Zhu; Yan-qiu Wei (Current Pharmacology Reports, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

Enhanced catalytic activities and modified substrate preferences for taxoid 10β-O-acetyl transferase mutants by engineering catalytic histidine residues - Lin-Feng You; Jia-Jun Huang; Tao Wei; Shu-Ling Lin; Bing-Hua Jiang; Li-Qiong Guo; Jun-Fang Lin (Biotechnology Letters, 2018)

Geochronology, geochemistry, Sr–Nd–Hf isotopic compositions, and petrogenetic and tectonic implications of Early Cretaceous intrusions associated with the Duolong porphyry–epithermal Cu–Au deposit, central Tibet - Shaogang Wei; Yang Song; Juxing Tang; Zhibo Liu; Qin Wang; Bin Lin; Jun Feng; Lin Hou; Wangxiu Danzhen (International Geology Review, 2018)

Targeted next-generation sequencing improves diagnosis of hereditary spastic paraplegia in Chinese patients - Cong Lu; Li-Xi Li; Hai-Lin Dong; Qiao Wei; Zhi-Jun Liu; Wang Ni; Aaron D. Gitler; Zhi-Ying Wu (Journal of Molecular Medicine, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Regional, age and respiratory-secretion-specific prevalence of respiratory viruses associated with asthma exacerbation: a literature review - Xue-yan Zheng; Yan-jun Xu; Wei-jie Guan; Li-feng Lin (Archives of Virology, 2018)

Biotransformation of ursolic acid by Alternaria longipes AS3.2875 - Chen-Xi Zhang; Wei-Jun Ma; Dai-Lin Liu; Xiu-Juan Jia; Yan-Min Zhao (Natural Product Research, 2018)

Correlation analyses revealed global microRNA–mRNA expression associations in human peripheral blood mononuclear cells - Lan Wang; Jiang Zhu; Fei-Yan Deng; Long-Fei Wu; Xing-Bo Mo; Xiao-Wei Zhu; Wei Xia; Fang-Fei Xie; Pei He; Peng-Fei Bing; Ying-Hua Qiu; Xiang Lin; et al. (Molecular Genetics and Genomics, 2018)

Variations in cadmium and nitrate co-accumulation among water spinach genotypes and implications for screening safe genotypes for human consumption - Lin Tang; Wei-jun Luo; Zhen-li He; Hanumanth Kumar Gurajala; Yasir Hamid; Kiran Yasmin Khan; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2018)

PBPK/PD assessment for Parkinson’s disease risk posed by airborne pesticide paraquat exposure - Yi-Hsien Cheng; Wei-Chun Chou; Ying-Fei Yang; Chi-Wei Huang; Chun Ming How; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Shu-Han You; Chung-Min Liao (Environmental Science and Pollution Research, 2018)

A new arbutin derivative from the leaves of Vaccinium dunalianum wight - Na Li; Wei-Lin Zeng; Xu-Lu Luo; Chong-Ren Yang; Ying-Jun Zhang; Yong Ding; Ping Zhao (Natural Product Research, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Iron supply prevents Cd uptake in Arabidopsis by inhibiting IRT1 expression and favoring competition between Fe and Cd uptake - Xiao Lin He; Shi Kan Fan; Jun Zhu; Mei Yan Guan; Xing Xing Liu; Yong Song Zhang; Chong Wei Jin (Plant and Soil, 2017)

Enhancement of simultaneous algicidal and denitrification of immobilized Acinetobacter sp. J25 with magnetic Fe3O4 nanoparticles - Jun feng Su; Dong hui Liang; Ting lin Huang; Li Wei; Min Ma; Jinsuo Lu (Environmental Science and Pollution Research, 2017)

Densoviruses in oyster Crassostrea ariakensis - Yan-Jun Kang; Wei Huang; A-li Zhao; Dan-Dan Lai; Lin Shao; Yan-Qin Shen; Xutao Deng; Eric Delwart; Wen Zhang (Archives of Virology, 2017)

Mixture risk assessment due to ingestion of arsenic, copper, and zinc from milkfish farmed in contaminated coastal areas - Yi-Jun Lin; Min-Pei Ling; Szu-Chieh Chen; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Hsien Cheng; Shu-Han You; Wei-Chun Chou; Ming-Chao Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Apigenin alleviates STZ-induced diabetic cardiomyopathy - Huang-Jun Liu; Yun-Lin Fan; Hai-Han Liao; Yuan Liu; Si Chen; Zhen-Guo Ma; Ning Zhang; Zheng Yang; Wei Deng; Qi-Zhu Tang (Molecular and Cellular Biochemistry, 2017)

Periodic increments in the jumbo squid (Dosidicus gigas) beak: a potential tool for determining age and investigating regional difference in growth rates - Bi Lin Liu; Xin Jun Chen; Yong Chen; Guan Yu Hu; Wei Yu; Jin Tao Wang; Jing Yuan Lin (Hydrobiologia, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Two cultivated legume plants reveal the enrichment process of the microbiome in the rhizocompartments - Xiao Xiao; Weimin Chen; Le Zong; Jun Yang; Shuo Jiao; Yanbing Lin; Entao Wang; Gehong Wei (Molecular Ecology, 2017)
The microbiomes of rhizocompartments (nodule endophytes, root endophytes, rhizosphere and root zone) in soya bean and alfalfa were analysed using high‐throughput sequencing to investigate the interactions among legume species, microorganisms and soil types. A clear hierarchical filtration of microbiota by plants was observed in the four rhizocompartments – the nodule endosphere, root endosphere, rhizosphere and root zone – as demonstrated by significant variations in the composition of the microbial community in the different compartments. The rhizosphere and root zone microbial communities were largely influenced by soil type, and the nodule and root endophytes were primarily determined by plant species. Diverse microbes inhabited the root nodule endosphere, and the corresponding dominant symbiotic rhizobia belonged to Ensifer for alfalfa and Ensifer – Bradyrhizobium for soya bean. The nonsymbiotic nodule endophytes were mainly Proteobacteria, Actinobacteria, Firmicutes and Bacteroidetes. The variation in root microbial communities was also affected by the plant growth stage. In summary, this study demonstrated that the enrichment process of nodule endophytes follows a hierarchical filtration and that the bacterial communities in nodule endophytes vary according to the plant species.

Characterization, sources and ecological risk assessment of polycyclic aromatic hydrocarbons in surface sediments from the mangroves of China - Dao-lai Zhang; Na Liu; Ping Yin; Zhi-gang Zhu; Jing-fang Lu; Xue-hui Lin; Xue-jun Jiang; Xian-wei Meng (Wetlands Ecology and Management, 2017)

Celastrol, produced by Tripterygium wilfordii Hook F. enhances defense response in cucumber seedlings against diverse environmental stresses - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Peng-xu Li; Jun-qiang Wu; Da-wei Zhang; Honghui Lin (Journal of Plant Biology, 2017)

Nestin Expression Is Associated with Poor Clinicopathological Features and Prognosis in Glioma Patients: an Association Study and Meta-analysis - Donglai Lv; Lin Lu; Zongtao Hu; Zhenle Fei; Meiqin Liu; Lei Wei; Jun Xu (Molecular Neurobiology, 2017)

The biochemical and toxicological responses of earthworm (Eisenia fetida) following exposure to nanoscale zerovalent iron in a soil system - Jun Liang; Xiaoqian Xia; Wei Zhang; Waqas Qamar Zaman; Kuangfei Lin; Shuangqing Hu; Zhifen Lin (Environmental Science and Pollution Research, 2017)

A novel trichosanthin fusion protein with increased cytotoxicity to tumor cells - Bing Lin; Xu-Zhong Yang; Xue-Wei Cao; Tao-Zhu Zhang; Fu-Jun Wang; Jian Zhao (Biotechnology Letters, 2017)

MicroRNA-9 Mediates the Cell Apoptosis by Targeting Bcl2l11 in Ischemic Stroke - Na Wei; Lin Xiao; Rui Xue; Dandan Zhang; Jun Zhou; Huayan Ren; Si Guo; Jingjing Xu (Molecular Neurobiology, 2016)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Rice false smut fungus hijacks the rice nutrients supply by blocking and mimicking the fertilization of rice ovary - Jie‐Hui Song; Wei Wei; Bo Lv; Yang Lin; Wei‐Xiao Yin; You‐Liang Peng; Guido Schnabel; Jun‐Bin Huang; Dao‐Hong Jiang; Chao‐Xi Luo (Environmental Microbiology, 2016)
Summary Rice false smut disease is an increasing threat to rice production in the world. Despite of best efforts, research for the infection of the fungus has yielded equivocal and conflicting results about where and how the infection is initiated and developed. Here we show a stepwise infection pattern and sophisticated regulation during this process. Initial infection occurred on the filaments, which prevented the production of mature pollen thus blocked the pollination. In the following days, the pathogen invaded the stigmas and styles, occasionally the ovaries. Expression analysis indicated that the fungus mimicked a successful fertilization process and enabled the continuous supply of nutrients for fungus to produce false smut balls. The stepwise infection of flower organs and mimicry of ovary fertilization unveiled in this study guided the rice plant into supplying nutrients for false smut ball development and represents a new and unique biological process of host pathogen interactions.

Minocycline ameliorates d-galactose-induced memory deficits and loss of Arc/Arg3.1 expression - Xu Li; Fen Lu; Wei Li; Jun Xu; Xiao-Jing Sun; Ling-Zhi Qin; Qian-Lin Zhang; Yong Yao; Qing-Kai Yu; Xin-Liang Liang (Molecular Biology Reports, 2016)

BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2016)

Assessing exposure risks for freshwater tilapia species posed by mercury and methylmercury - Yi-Hsien Cheng; Yi-Jun Lin; Shu-Han You; Ying-Fei Yang; Chun Ming How; Yi-Ting Tseng; Wei-Yu Chen; Chung-Min Liao (Ecotoxicology, 2016)

Biotransformation of gypenoside XVII to compound K by a recombinant β-glucosidase - Fei-Liang Zhong; Wei-Wei Dong; Songquan Wu; Jun Jiang; Deok-Chun Yang; Donghao Li; Lin-Hu Quan (Biotechnology Letters, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Three duplication events and variable molecular evolution characteristics involved in multiple GGPS genes of six Solanaceae species - FENG LI; CHUNYANG WEI; CHAN QIAO; ZHENXI CHEN; PENG WANG; PAN WEI; RAN WANG; LIFENG JIN; JUN YANG; FUCHENG LIN; ZHAOPENG LUO (Journal of Genetics, 2016)

Proanthocyanidins accelerate the germination of cucumber (Cucumis sativus L.) seeds - Li-jun Zhu; Xing-guang Deng; Li-juan Zou; Jun-qiang Wu; Da-wei Zhang; Hong-hui Lin (Journal of Plant Biology, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

A new directional query method for polygon dataset in spatial database - Wei Hua Lin; Xiao Jun Tan; Fu Jiang Liu; Yan Yu; Wei Ming Wang (Earth Science Informatics, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Effects of glutamate on growth, antioxidant capacity, and antioxidant-related signaling molecule expression in primary cultures of fish enterocytes - Jun Jiang; Dan Shi; Xiao-Qiu Zhou; Long Yin; Lin Feng; Yang Liu; Wei-Dan Jiang; Ye Zhao (Fish Physiology and Biochemistry, 2015)

Ecological status classification of the Taizi River Basin, China: a comparison of integrated risk assessment approaches - Juntao Fan; Elena Semenzin; Wei Meng; Elisa Giubilato; Yuan Zhang; Andrea Critto; Alex Zabeo; Yun Zhou; Sen Ding; Jun Wan; Mengchang He; Chunye Lin (Environmental Science and Pollution Research, 2015)

Potential Neurogenesis of Human Adipose-Derived Stem Cells on Electrospun Catalpol-Loaded Composite Nanofibrous Scaffolds - Jian-Hui Guo; Yang Liu; Zheng-Jun Lv; Wen-Juan Wei; Xin Guan; Qing-Lin Guan; Zhi-Qian Leng; Jing-Yuan Zhao; Hui Miao; Jing Liu (Annals of Biomedical Engineering, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Isolation of a new flavanone from Daidai fruit and hypolipidemic activity of total flavonoids extracts - Ling-Jun Zeng; Dan Chen; Qing-De Huang; Qun Huang; Yun-Fang Lian; Wei-Wei Cai; Hua-Ping Zeng; Yi-Li Lin (Natural Product Research, 2015)

Expression and Functional Analysis of a Pathogenesis-Related Protein 1 Gene, TcLr19PR1, Involved in Wheat Resistance Against Leaf Rust Fungus - Lin Gao; Shen Wang; Xiao-Ying Li; Xue-Jun Wei; Yan-Jun Zhang; Hai-Yan Wang; Da-Qun Liu (Plant Molecular Biology Reporter, 2015)

The Neural Stem Cell Microenvironment: Focusing on Axon Guidance Molecules and Myelin-Associated Factors - Chao-Jin Xu; Jun-Ling Wang; Wei-Lin Jin (Journal of Molecular Neuroscience, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Multiple Mesozoic magma processes formed the 240–185 Ma composite Weishan pluton, South China: evidence from geochronology, geochemistry, and Sr-Nd isotopes - Xing Ding; Wei-Dong Sun; Wei-Feng Chen; Pei-Rong Chen; Tao Sun; Sai-Jun Sun; Chiou-Ting Lin; Fu-Kun Chen (International Geology Review, 2015)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

Microstructural and mineral analysis on the fault gouge in the coseismic shear zone of the 2008 M w 7.9 Wenchuan earthquake - Ren-mao Yuan; Bing-liang Zhang; Xi-wei Xu; Chuan-yong Lin; Zhu-jun Han (International Journal of Earth Sciences, 2015)

High-efficiency propagation of Chinese water chestnut [Eleocharis dulcis (Burm.f.) Trin. ex Hensch] using a temporary immersion bioreactor system - Meiping Gao; Wen Jiang; Shaolong Wei; Zhicheng Lin; Binghua Cai; Liu Yang; Cong Luo; Xinhua He; Jun Tan; Lijuan Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Escitalopram Ameliorates Forskolin-Induced Tau Hyperphosphorylation in HEK239/tau441 Cells - Qing-Guo Ren; Yan-Juan Wang; Wei-Gang Gong; Qi-Da Zhou; Lin Xu; Zhi-Jun Zhang (Journal of Molecular Neuroscience, 2015)

Effect of dietary glutamine on growth performance, non-specific immunity, expression of cytokine genes, phosphorylation of target of rapamycin (TOR), and anti-oxidative system in spleen and head kidney of Jian carp (Cyprinus carpio var. Jian) - Kai Hu; Jing-Xiu Zhang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Identification and localized expression of putative K+/H+ antiporter genes in Arabidopsis - Lei Han; Jun Lin Li; Li Wang; Wei Ming Shi; Yan Hua Su (Acta Physiologiae Plantarum, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Association of soil arsenic and nickel exposure with cancer mortality rates, a town-scale ecological study in Suzhou, China - Kai Chen; Qi Lin Liao; Zong Wei Ma; Yang Jin; Ming Hua; Jun Bi; Lei Huang (Environmental Science and Pollution Research, 2015)

Regional response of dengue fever epidemics to interannual variation and related climate variability - Chung-Min Liao; Tang-Luen Huang; Yi-Jun Lin; Shu-Han You; Yi-Hsien Cheng; Nan-Hung Hsieh; Wei-Yu Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Degradation and dechlorination of pentachlorophenol by microwave-activated persulfate - Chengdu Qi; Xitao Liu; Wei Zhao; Chunye Lin; Jun Ma; Wenxiao Shi; Qu Sun; Hao Xiao (Environmental Science and Pollution Research, 2015)

Isolation and characterization of 25 polymorphic microsatellite loci from the Hynobius maoershanensis (Caudata: Hynobiidae) - Bing-jie Lin; Hua-yuan Huang; Zhong-hui Wei; Ze-ning Chen; Shao-neng Wang; Zheng-jun Wu (Conservation Genetics Resources, 2015)

Effect of JEZTC, a synthetic compound, on proliferation and phenotype maintenance of rabbit articular chondrocytes in vitro - Lei Liu; Qin Liu; Xiao Lin; Qing Jun Wei; Li Zheng (In Vitro Cellular & Developmental Biology - Animal, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of catechins on Agrobacterium-mediated genetic transformation of Camellia sinensis - Da-Peng Song; Lin Feng; M. M. Rana; Ming-Jun Gao; Shu Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Role of SIRT1 in Streptococcus pneumoniae-induced human β-defensin-2 and interleukin-8 expression in A549 cell - Li Lin; Shun-hang Wen; Shu-zhen Guo; Xiao-yan Su; Hu-jun Wu; Lei Chong; Hai-lin Zhang; Wei-xi Zhang; Chang-chong Li (Molecular and Cellular Biochemistry, 2014)

Quantitative trait loci analysis of individual and total isoflavone contents in soybean seeds - HAI JUN ZHANG; JING WEN LI; YA JING LIU; WEN ZHU JIANG; XING LIN DU; LIN LI; XIAO WEI Li; LIAN TAI SU; QING YU WANG; YING WANG (Journal of Genetics, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

Influence of casein phosphopeptide-amorphous calcium phosphate application, smear layer removal, and storage time on resin-dentin bonding - Jun Lin; Wei-ying Zheng; Peng-ruo-feng Liu; Ning Zhang; Hui-ping Lin; Yi-jing Fan; Xin-hua Gu; Oliver Vollrath; Christian Mehl (Journal of Zhejiang University-SCIENCE B, 2014)

Notch inhibition promotes fetal liver stem/progenitor cells differentiation into hepatocytes via the inhibition of HNF-1β - Tao Wang; Tao Chen; Hong-yin Liang; Hong-tao Yan; Ning Lin; Li-ye Liu; Hao Luo; Zhu Huang; Nan-lin Li; Wei-hui Liu; Li-jun Tang (Cell and Tissue Research, 2014)

The effects of dietary thiamin on oxidative damage and antioxidant defence of juvenile fish - Xue-Yin Li; Hui-Hua Huang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Shu-Hong Li; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Identification of the substrate recognition region in the Δ6-fatty acid and Δ8-sphingolipid desaturase by fusion mutagenesis - Li-Ying Song; Yan Zhang; Shu-Fen Li; Jun Hu; Wei-Bo Yin; Yu-Hong Chen; Shan-Ting Hao; Bai-Lin Wang; Richard R.-C. Wang; Zan-Min Hu (Planta, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

A new benzopyran derivative from Pseuduvaria indochinensis Merr. - Cai-Gui Zhao; Ming-Jun Yao; Jin-Wei Yang; Ya-Lin Chai; Xiao-Dong Sun; Cheng-Shan Yuan (Natural Product Research, 2014)

Genome-wide analysis of the bHLH transcription factor family in Chinese cabbage (Brassica rapa ssp. pekinensis) - Xiao-Ming Song; Zhi-Nan Huang; Wei-Ke Duan; Jun Ren; Tong-Kun Liu; Ying Li; Xi-Lin Hou (Molecular Genetics and Genomics, 2014)

ZxSOS1 is essential for long-distance transport and spatial distribution of Na+ and K+ in the xerophyte Zygophyllum xanthoxylum - Qing Ma; Yi-Xiao Li; Hui-Jun Yuan; Jing Hu; Li Wei; Ai-Ke Bao; Jin-Lin Zhang; Suo-Min Wang (Plant and Soil, 2014)

Pemetrexed downregulates ERCC1 expression and enhances cytotoxicity effected by resveratrol in human nonsmall cell lung cancer cells - Ruey-Shyang Chen; Jen-Chung Ko; Hsien-Chun Chiu; Ting-Yu Wo; Yi-Jhen Huang; Sheng-Chieh Tseng; Huang-Jen Chen; Yu-Ching Huang; Yi-Jun Jian; Wei-Ting Lee; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

The expression and regulation of DFNA5 in human hepatocellular carcinoma DFNA5 in hepatocellular carcinoma - Cong-Jun Wang; Lin Tang; Dong-Wei Shen; Chao Wang; Qiong-Ying Yuan; Wei Gao; Yong-Kun Wang; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Genetic phylogeography and maternal lineages of 18 Chinese black goat breeds - Tao Zhong; Qian Jun Zhao; Li Li Niu; Jie Wang; Peng Fei Jin; Wei Zhao; Lin Jie Wang; Li Li; Hong Ping Zhang; Yue Hui Ma (Tropical Animal Health and Production, 2013)

Nitrate nutrition enhances nickel accumulation and toxicity in Arabidopsis plants - Yan Hu; Nai Shan Wang; Xu Jun Hu; Xian Yong Lin; Ying Feng; Chong Wei Jin (Plant and Soil, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Abnormal baseline brain activity in patients with HBV-related cirrhosis without overt hepatic encephalopathy revealed by resting-state functional MRI - Xiao-Fei Lv; Min Ye; Lu-Jun Han; Xue-Lin Zhang; Pei-Qiang Cai; Gui-Hua Jiang; Ying-Wei Qiu; Shi-Jun Qiu; Yao-Pan Wu; Kai Liu; Zhen-Yin Liu; Pei-Hong Wu; et al. (Metabolic Brain Disease, 2013)

Region-specific role of Rac in nucleus accumbens core and basolateral amygdala in consolidation and reconsolidation of cocaine-associated cue memory in rats - Zeng-Bo Ding; Ping Wu; Yi-Xiao Luo; Hai-Shui Shi; Hao-Wei Shen; Shen-Jun Wang; Lin Lu (Psychopharmacology, 2013)

Acute ketamine induces hippocampal synaptic depression and spatial memory impairment through dopamine D1/D5 receptors - Ting-Ting Duan; Ji-Wei Tan; Qiang Yuan; Jun Cao; Qi-Xin Zhou; Lin Xu (Psychopharmacology, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Evaluation of Burma Reed as Substrate for Production of Pleurotus eryngii - Xian-lu Zeng; Jun-fang Lin; Li-qiong Guo; Rong-wei Cao; Wei-qiang Zeng (Indian Journal of Microbiology, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

The Flexible Global Ocean-Atmosphere-Land system model, Spectral Version 2: FGOALS-s2 - Qing Bao; Pengfei Lin; Tianjun Zhou; Yimin Liu; Yongqiang Yu; Guoxiong Wu; Bian He; Jie He; Lijuan Li; Jiandong Li; Yangchun Li; Hailong Liu; et al. (Advances in Atmospheric Sciences, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Chemical Composition and Sensory Evaluation of Fermented Tea with Medicinal Mushrooms - Wei-Fang Bai; Xin-Yue Guo; Li-Qing Ma; Li-Qiong Guo; Jun-Fang Lin (Indian Journal of Microbiology, 2013)

Dynamic distribution and tissue tropism of infectious laryngotracheitis virus in experimentally infected chickens - Lin-Guo Wang; Jun Ma; Chun-Yi Xue; Wei Wang; Chao Guo; Feng Chen; Jian-Ping Qin; Ning-Hai Huang; Ying-Zuo Bi; Yong-Chang Cao (Archives of Virology, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Comparative study of four rice cultivars with different levels of cadmium tolerance - Xiao Wang; Zhong-Wei Zhang; Shi-Hua Tu; Wen-Qiang Feng; Fei Xu; Feng Zhu; Da-Wei Zhang; Jun-Bo Du; Shu Yuan; Hong-Hui Lin (Biologia, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Association between polymorphisms of the CYP11A1 gene and polycystic ovary syndrome in Chinese women - Cheng-wei Zhang; Xin-lin Zhang; Yan-jie Xia; Yun-xia Cao; Wen-jun Wang; Pei Xu; Ye-na Che; Xiao-ke Wu; Long Yi; Qian Gao; Yong Wang (Molecular Biology Reports, 2012)

Analysis of Isocitrate Dehydrogenase 1 Mutation in 97 Patients with Glioma - You-Xin Zhou; Jun-Xiang Wang; Ming Feng; Chun-Ming Sun; Ting Sun; Gui-Lin Chen; Zi-Wei Du (Journal of Molecular Neuroscience, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Apolipoprotein A-I mimetic peptide D-4F promotes human endothelial progenitor cell proliferation, migration, adhesion though eNOS/NO pathway - Zhengang Zhang; Jianhua Qun; Chunmei Cao; Jun Wang; Wei Li; Yong Wu; Lin Du; Pei Zhao; Kaizheng Gong (Molecular Biology Reports, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Role of calcineurin in the VTA in rats behaviorally sensitized to methamphetamine - Jun Wang; Li-Li Sun; Wei-Li Zhu; Yan Sun; Jian-Feng Liu; Lin Lu; Jie Shi (Psychopharmacology, 2012)

Inhibitor of DNA-binding-1/inhibitor of differentiation-1 (ID-1) is implicated in various aspects of gastric cancer cell biology - Wei Li; Chun-Hua Zhang; Yi-Lin Hong; Jun Li; Yong-Mei Hu; Cui-Fen Zhao (Molecular Biology Reports, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

The accumulation of pigment in fiber related to proanthocyanidins synthesis for brown cotton - Tingchun Li; Honghong Fan; Zhengpeng Li; Jun Wei; Yi Lin; Yongping Cai (Acta Physiologiae Plantarum, 2012)

Expression, purification, and characterization of alanine racemase from Pseudomonas putida YZ-26 - Jun-Lin Liu; Xiao-Qin Liu; Ya-Wei Shi (World Journal of Microbiology and Biotechnology, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Chronic alcohol intake-induced oxidative stress and apoptosis: role of CYP2E1 and calpain-1 in alcoholic cardiomyopathy - Ling Jing; Cheng-mei Jin; Shan-shan Li; Feng-min Zhang; Lin Yuan; Wei-min Li; Ying Sang; Shuang Li; Li-jun Zhou (Molecular and Cellular Biochemistry, 2012)

Inhibition of Lymphoma Cell Proliferation by Peroxisomal Proliferator-Activated Receptor-γ Ligands via Wnt Signaling Pathway - Jia-Jun Liu; Xue-Jun Dai; Yan Xu; Pei-Qing Liu; Yong Zhang; Xiao-Dan Liu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang (Cell Biochemistry and Biophysics, 2012)

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)

CXCR4 positive cells from Lewis lung carcinoma cell line have cancer metastatic stem cell characteristics - Wei-Qi Nian; Fang-Lin Chen; Xu-Jun Ao; Zheng-Tang Chen (Molecular and Cellular Biochemistry, 2011)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Biodegradation of leuco derivatives of triphenylmethane dyes by Sphingomonas sp. CM9 - Jun Wu; Liguan Li; Hongwei Du; Lijuan Jiang; Qiong Zhang; Zhongbo Wei; Xiaolin Wang; Lin Xiao; Liuyan Yang (Biodegradation, 2011)

Collateral vessel growth induced by femoral artery ligature is impaired by denervation - Ming-ying Luo; Bao-lin Yang; Feng Ye; Xiaoqiong Wu; Song Peng; Bin Yi; Wei Wang; Wu Zhu; Hua Luo; Jian-Guo Wen; Wei-Jun Cai; Jutta Schaper; et al. (Molecular and Cellular Biochemistry, 2011)

Assessing the potential exposure risk and control for airborne titanium dioxide and carbon black nanoparticles in the workplace - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2011)

PPARγ Agonist Suppresses TLR4 Expression and TNF-α Production in LPS Stimulated Monocyte Leukemia Cells - Chun-Zhi Wang; Yong Zhang; Xu-Dong Li; Yuan Hu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang; Pei-Qing Liu; Jia-Jun Liu (Cell Biochemistry and Biophysics, 2011)

Late Mesozoic extensional tectonics of the Liaodong Peninsula massif: Response of crust to continental lithosphere destruction of the North China Craton - Wei Lin; QingChen Wang; Jun Wang; Fei Wang; Yang Chu; Ke Chen (Science China Earth Sciences, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Large-Eddy Simulation of the Wind Field and Plume Dispersion Within Different Obstacle Arrays Using a Dynamic Mixing Length Subgrid-Scale Model - Zhao Lin Gu; Jian Ying Jiao; Jun Wei Su (Boundary-Layer Meteorology, 2011)

Investigation of the Interaction Between the Ser447Term Polymorphism of Lipoprotein Lipase and the Stroke-Related Risk Factors in Ischemic Stroke - Yumei Yang; Danhua Du; Peng Gao; Xuan Zhang; Ning Wu; Feng Wang; Zhenqi Wang; Lin Ye; Jiang Wu; Ian L. Megson; Jun Wei (Translational Stroke Research, 2011)

RRM1 gene expression in peripheral blood is predictive of shorter survival in Chinese patients with advanced non-small-cell lung cancer treated by gemcitabine and platinum - Lin-run Wang; Guo-bing Zhang; Jian Chen; Jun Li; Ming-wei Li; Nong Xu; Yang Wang; Jian-zhong Shen Tu (Journal of Zhejiang University-SCIENCE B, 2011)

Comparative expression analysis of dehydrins between two barley varieties, wild barley and Tibetan hulless barley associated with different stress resistance - Jun-Bo Du; Shu Yuan; Yang-Er Chen; Xin Sun; Zhong-Wei Zhang; Fei Xu; Ming Yuan; Jing Shang; Hong-Hui Lin (Acta Physiologiae Plantarum, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Honokiol: an effective inhibitor of high-glucose-induced upregulation of inflammatory cytokine production in human renal mesangial cells - Jian-Ping Wu; Wei Zhang; Fang Wu; Ying Zhao; Lin-Fang Cheng; Jun-Jun Xie; Hang-Ping Yao (Inflammation Research, 2010)

A fusion fragment from Flt-1 and KDR, acted as VEGF decoy receptor and exhibited anti-tumor function - Zhuang-Lin Li; Xue-Jing Yao; Wei-Feng Liu; Guan-Jun Chen (Biotechnology Letters, 2010)

Activation of PPARδ promotes mitochondrial energy metabolism and decreases basal insulin secretion in palmitate-treated β-cells - Li Jiang; Jun Wan; Lin-qiu Ke; Qing-guo Lü; Nan-wei Tong (Molecular and Cellular Biochemistry, 2010)

Genetic analysis of the VP1 region of enterovirus 71 reveals the emergence of genotype A in central China in 2008 - Haiyang Yu; Wei Chen; Hongwei Chang; Renshu Tang; Jun Zhao; Lin Gan; Boyu Liu; Jason Chen; Mingli Wang (Virus Genes, 2010)

Interspecific hybrids between Chrysanthemum grandiflorum (Ramat.) Kitamura and C. indicum (L.) Des Moul. and their drought tolerance evaluation - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Total and speciated arsenic levels in rice from China - Feng Liang; Yulan Li; Guilin Zhang; Mingguang Tan; Jun Lin; Wei Liu; Yan Li; Wenwei Lu (Food Additives & Contaminants: Part A, 2010)

The Chebyshev spectral element method using staggered predictor and corrector for elastic wave simulations - Cheng-Xuan Che; Xiu-Ming Wang; Wei-Jun Lin (Applied Geophysics, 2010)

Evidence for the Formation of the Male Gynogenetic Fish - Shaojun Liu; Qinbo Qin; Yuequn Wang; Hong Zhang; Rurong Zhao; Chun Zhang; Jing Wang; Wei Li; Lin Chen; Jun Xiao; Kaikun Luo; Min Tao; et al. (Marine Biotechnology, 2010)

Analysis of two sequence variants in peroxisome proliferator activated receptor gamma gene in Tajik population at high altitudes and Han population at low altitudes in China - Xiao-Ling Liu; Feng-Lin Zhang; Zhi-Yong Zhou; Hua-Lu Zhao; Guo-Min Shen; Wu-Yun Baohan; Zi-Yuan Duan; Wei Li; Jun-Wu Zhang (Molecular Biology Reports, 2010)

Factors affecting seed set in the crosses between Dendranthema grandiflorum (Ramat.) Kitamura and its wild species - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Formation of shaped barium sulfate-dye hybrids: waste dye utilization for eco-friendly treatment of wastewater - Hong-Wen Gao; Jing Lin; Wei-Ying Li; Zhang-Jun Hu; Ya-Lei Zhang (Environmental Science and Pollution Research, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Multicentre evaluation of the Elecsys® hepatitis B surface antigen II assay for detection of HBsAg in comparison with other commercially available assays - Ji-Dong Jia; Ma Hong; Lai Wei; Xin-Xin Zhang; Yuan-Li Mao; Lan-Lan Wang; Zhi-Liang Gao; Jin-Lin Hou; Jun Zhang (Medical Microbiology and Immunology, 2009)

Establishment and characterization of a fibroblast cell line from the Mongolian horse - Lin-feng Li; Wei-jun Guan; Yue Hua; Xiu-juan Bai; Yue-hui Ma (In Vitro Cellular & Developmental Biology - Animal, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Overexpression of Thellungiella halophila H+-PPase (TsVP) in cotton enhances drought stress resistance of plants - Su-Lian Lv; Li-Jun Lian; Pei-Lin Tao; Zhao-Xia Li; Ke-Wei Zhang; Ju-Ren Zhang (Planta, 2009)

A new eremophilenolactone from Senecio nemorensis - Fan Jun Meng; Yan Nan Xiao; Rui Jian Zhao; Hong Zhao; Qing Lin Ma; Wei Dong Xie (Natural Product Research, 2009)

Cistanche deserticola Ma cultivated as a new crop in China - Rong Xu; Jun Chen; Shi-Lin Chen; Tong-Ning Liu; Wei-Cheng Zhu; Jiang Xu (Genetic Resources and Crop Evolution, 2009)

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock - Yuan-qiang Lu; Wei-dong Huang; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Cloning and expression of selenocysteine methyltransferase cDNA from Camellia sinensis - Lin Zhu; Chang-Jun Jiang; Wei-Wei Deng; Xuan Gao; Rang-Jian Wang; Xiao-Chun Wan (Acta Physiologiae Plantarum, 2008)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

A trypsin inhibitor from Cassia obtusifolia seeds: isolation, characterization and activity against Pieris rapae - Hai Liao; Wei Ren; Zhuang Kang; Jia-Hong Jiang; Xiao-Jun Zhao; Lin-Fang Du (Biotechnology Letters, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

The solution structure of rat Aβ-(1–28) and its interaction with zinc ion: insights into the scarcity of amyloid deposition in aged rat brain - Jin Huang; Yong Yao; Jun Lin; Yong-Hao Ye; Wei-Yin Sun; Wen-Xia Tang† (JBIC Journal of Biological Inorganic Chemistry, 2004)

Daily changes in components of xanthophyll cycle and antioxidant systems in leaves of rice at different developing stage - Cheng-Wei Yang; Yi-Zhu Chen; Chang-Lian Peng; Duan Jun; Gui-Zhu Lin (Acta Physiologiae Plantarum, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Activation of Signal Transduction Kinases by Tamoxifen - Jauh-Lin Duh; Rong Yu; Jie-Jun Jiao; George A. Matwyshyn; Wei Li; Tse-Hua Tan; A.-N. Tony Kong (Pharmaceutical Research, 1997)